Adhesive sheet having an adhesive sheet and a release liner

KR103017666B1Active Publication Date: 2026-09-11NITTO DENKO CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020227036301
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-23
Filing Date
2021-03-24
Publication Date
2026-09-11
Estimated Expiration
2041-03-24

Smart Images

  • Figure 112022109939054-PCT00004_ABST
    Figure 112022109939054-PCT00004_ABST
Patent Text Reader

Abstract

An adhesive sheet comprising an adhesive layer is provided. The adhesive sheet has an adhesive surface formed by the adhesive layer. The adhesive layer has a refractive index greater than 1.570, a total light transmittance of 86% or more, and a haze value of 3.0% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an adhesive sheet comprising an adhesive sheet and a release liner.

[0002] The present application claims priority based on Japanese Patent Application No. 2020-052408 filed on March 24, 2020, Japanese Patent Application No. 2020-166425 filed on September 30, 2020, and Japanese Patent Application No. 2021-049058 filed on March 23, 2021, the entire contents of which are incorporated by reference into this specification. Background Technology

[0003] Generally, adhesives (also called pressure-sensitive adhesives; hereinafter the same) exhibit a flexible solid (viscoelastic) state in the temperature range near room temperature and possess the property of easily adhering to a substrate by pressure. Taking advantage of this property, adhesives are widely used for purposes such as bonding, fixing, and protection in various industrial fields, ranging from home appliances to automobiles, various machinery, electrical equipment, and electronic equipment. As an example of an application of adhesives, they are used to bond other components with polarizing films, phase difference films, cover window members, and various other light-transmitting members in display devices such as liquid crystal displays or organic EL displays. Patent documents 1 and 2 can be cited as technical literature regarding adhesives for optical members. Prior art literature

[0004] Japanese Patent Application Publication No. 2014-169382 and Japanese Patent Application Publication No. 2017-128732 The problem to be solved

[0005] Patent documents 1 and 2 propose an adhesive composition having (meth)acrylic acid ester polymers containing monomers having multiple aromatic rings as monomer units as main components, and an adhesive formed by crosslinking said adhesive composition, but they do not disclose a specific adhesive having a refractive index exceeding 1.570. Meanwhile, a technique to increase the refractive index by incorporating particles made of inorganic materials with a high refractive index (e.g., inorganic particles such as zirconium oxide particles or titanium oxide particles) into a resin is also known, but adhesives incorporating inorganic particles have a trade-off relationship between the refractive index and adhesive properties (e.g., peel strength, flexibility, etc.), making it difficult to apply to the field of adhesives. In particular, for adhesives intended for optical applications, it is necessary to consider the influence on optical properties (e.g., total light transmittance, haze, etc.) when incorporating inorganic particles. For this reason, there is no known adhesive sheet that exhibits practical adhesive performance by having an adhesive layer that combines a refractive index exceeding 1.570 with good optical properties (transparency) suitable for optical applications.

[0006] The present invention was created in consideration of the above situation and aims to provide an adhesive sheet having an adhesive layer that combines a high refractive index and good optical properties. Another objective of the present invention is to provide an adhesive sheet having a release liner comprising the adhesive sheet. means of solving the problem

[0007] According to this specification, an adhesive sheet is provided that includes an adhesive layer and has an adhesive surface formed by said adhesive layer. The adhesive layer has a refractive index greater than 1.570, a total light transmittance of 86% or more, and a haze value of 3.0% or less. By having a highly transparent adhesive layer, the adhesive sheet is useful as a high-refractive-index adhesive sheet suitable for optical applications. Furthermore, by attaching the adhesive surface of said adhesive sheet to a substrate, a high-refractive-index adhesive layer can be easily disposed on said substrate.

[0008] In some embodiments, the thickness of the adhesive layer is 5 μm or more. With an adhesive layer having such a thickness, good adhesive properties are easily obtained. In addition, since an adhesive layer having such a thickness absorbs irregularities that may exist on the surface of the substrate and is easy to bond to the substrate with good adhesion, a high refractive index adhesive layer can be appropriately provided on the substrate.

[0009] The adhesive sheet according to several embodiments has a peel strength (adhesion strength) of 3 N / 25 mm or more against a glass plate. Having such adhesion strength is desirable from the perspective of bonding reliability with the substrate.

[0010] In some embodiments, the adhesive surface has an arithmetic mean roughness Ra of 100 nm or less. Having such a highly smooth adhesive surface is desirable from the perspective of optical homogeneity. For example, in a usage mode in which light is emitted through the adhesive surface (such as an adhesive sheet placed on the viewing side rather than a self-luminous element in a light-emitting device), the occurrence of luminance non-uniformity caused by the surface condition of the adhesive layer can be suppressed.

[0011] In some embodiments, the water absorption rate of the adhesive layer is 1.0% or less. With an adhesive layer having a low water absorption rate, dimensional changes in the adhesive layer caused by fluctuations in the amount of moisture in the adhesive layer can be suppressed. By doing so, warping of the adhesive sheet or the substrate to which the adhesive sheet is attached can be suppressed.

[0012] In some embodiments, the adhesive sheet is configured as a laminate comprising the adhesive layer and a light-transmitting substrate (e.g., a resin film). By attaching the adhesive sheet with such a configuration to a substrate, a structure in which the substrate and the light-transmitting substrate are laminated through the adhesive layer with a high refractive index can be easily formed.

[0013] In some embodiments, the adhesive sheet is a double-sided adhesive sheet comprising the adhesive layer. The double-sided adhesive sheet comprising the adhesive layer has excellent flexibility in that it does not have a non-removable substrate (support substrate). With such a double-sided adhesive sheet that does not have a non-removable substrate (hereinafter also referred to as a substrate-free double-sided adhesive sheet), a high-refractive-index adhesive layer can be easily installed on a substrate, and a highly flexible bond can be formed between the substrate and another member through the adhesive sheet.

[0014] In addition, according to this specification, an adhesive sheet having a release liner is provided, comprising an adhesive sheet of any of the types disclosed herein and a release liner disposed on the adhesive surface of the adhesive sheet. The adhesive sheet disclosed herein may be preferably used in a manner in which the release liner is peeled off from the adhesive surface before attachment to a substrate, by manufacturing, storing, distributing, processing, etc., in the form of an adhesive sheet having a release liner disposed on the adhesive surface.

[0015] In addition, a suitable combination of each element described in this specification may also be included within the scope of the invention for which patent protection is sought by this patent application. Brief explanation of the drawing

[0016] FIG. 1 is a cross-sectional view schematically illustrating the configuration of an adhesive sheet according to one embodiment. FIG. 2 is a cross-sectional view schematically illustrating the configuration of an adhesive sheet according to another embodiment. FIG. 3 is a cross-sectional view schematically illustrating an optical member having an adhesive sheet attached to an optical member, wherein the adhesive sheet according to one embodiment is attached to the optical member. Specific details for implementing the invention

[0017] Suitable embodiments of the present invention are described below. Matters other than those specifically mentioned in this specification and matters necessary for the implementation of the present invention can be understood by those skilled in the art based on the teachings regarding the implementation of the invention described in this specification and the technical common sense at the time of filing. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in the relevant field.

[0018] In addition, in the drawings below, members and parts exhibiting the same function may be described using the same reference numerals, and redundant descriptions may be omitted or simplified. Furthermore, the embodiments described in the drawings are schematic for the purpose of clearly explaining the present invention and do not necessarily represent the exact size or scale of the actual product provided.

[0019] In this specification, a self-luminous element refers to a light-emitting element capable of controlling luminous brightness by a flowing current value. A self-luminous element may be composed of a single body or may be composed of an assembly. Specific examples of a self-luminous element include light-emitting diodes (LEDs) and organic ELs, but are not limited thereto. When a light-emitting device is mentioned in this specification, the light-emitting device may include such a self-luminous element as a component. Examples of the light-emitting device include a light source module device used as lighting (e.g., a planar light-emitting module) and a display device forming pixels, but are not limited thereto.

[0020] <Composition of adhesive sheet>

[0021] In accordance with this specification, an adhesive sheet having an adhesive surface formed by an adhesive layer is provided. The adhesive sheet may be an adhesive sheet having a substrate having an adhesive layer on one or both sides of a non-removable substrate (support substrate), or it may be an adhesive sheet without a substrate, such as one in which the adhesive layer is retained and supported by a release liner (i.e., an adhesive sheet that does not have a non-removable substrate; typically, an adhesive sheet composed of an adhesive layer). The concept of an adhesive sheet as described herein may include what are referred to as adhesive tape, adhesive label, adhesive film, etc. The adhesive sheet disclosed herein may be in the form of a roll or a single sheet. Alternatively, it may be an adhesive sheet processed into a variety of shapes.

[0022] An example configuration of the adhesive sheet disclosed herein is illustrated in FIG. 1. The adhesive sheet (1) is configured as a single-sided adhesive sheet (single-sided adhesive sheet) comprising an adhesive layer (10) having a first surface (10A) that serves as a bonding surface (adhesive surface) to a substrate, and a support substrate (20) laminated on a second surface (10B) of the adhesive layer (10). The second surface (10B) of the adhesive layer (10) is bonded to a first surface (non-removable surface) (20A) of the support substrate (20). For example, a plastic film such as a polyester film may be used as the support substrate (20). For example, the support substrate (20) may be an optical film such as a polarizing plate. The adhesive sheet (1) before use (before attachment to the substrate) may be in the form of an adhesive sheet (50) having a release liner, wherein the adhesive surface (10A) is protected by a release liner (30) in which at least the adhesive layer side is a releaseable surface (release surface), as shown in FIG. 1, for example. Alternatively, the adhesive surface (10A) may be protected by winding or laminating so that the second surface (20B) of the support substrate (20) (a surface opposite to the first surface (20A), also called a back surface) is a release surface, and the adhesive surface (10A) is in contact with this second surface (20B). The adhesive layer (10) may be a single-layer structure, or a laminated structure in which two or more sub-adhesive layers of different compositions are directly in contact (i.e., not separated by a layer of non-adhesive material).

[0023] The adhesive sheet disclosed herein may be in the form of a non-substrate double-sided adhesive sheet consisting of an adhesive layer. As shown in FIG. 2, the non-substrate double-sided adhesive sheet (2) may be in a form in which, prior to use, the first surface (first adhesive surface) (10A) and the second surface (second adhesive surface) (10B) of the adhesive layer (10) are protected by a release liner (31, 32) in which at least the side of the adhesive layer is a releaseable surface (release surface). Alternatively, the back surface (the surface opposite to the adhesive side) of the release liner (31) may be a release surface, and the adhesive surfaces (10A, 10B) may be protected by winding or laminating so that the adhesive surface (10B) comes into contact with the back surface of the release liner (31). Such a double-sided adhesive sheet without a substrate can be used by bonding a substrate (preferably a light-transmitting substrate, which may be an optical member such as an optical film) to at least one of the first adhesive surface and the second adhesive surface. The adhesive layer constituting the double-sided adhesive sheet without a substrate may be a single-layer structure, similar to the adhesive layer (10) in the adhesive sheet (1) shown in FIG. 1, or a laminated structure in which two or more sub-adhesive layers with different compositions are directly in contact and laminated.

[0024] The adhesive sheet disclosed herein may be a component of an optical member having an adhesive sheet having an optical member bonded to at least one surface of an adhesive layer. For example, the adhesive sheet (1) shown in FIG. 1 may be a component of an optical member (100) having an adhesive sheet having an optical member (70) bonded to a first surface (10A) of an adhesive layer (10) as shown in FIG. 3. The optical member may be, for example, a glass plate, a resin film, a metal plate, etc. In addition, in the adhesive sheet (1) shown in FIG. 1, if the supporting substrate (20) is an optical member such as an optical film, the adhesive sheet (1) may be understood as an optical member having an adhesive sheet having an optical member bonded to a second surface (10B) of an adhesive layer (10).

[0025] Additionally, the adhesive sheet disclosed herein may be in the form of a double-sided adhesive sheet (a double-sided adhesive sheet having a substrate) having a supporting substrate having a non-removable first surface and a second surface, although not specifically illustrated therein, wherein a first adhesive layer is fixedly laminated on the first surface and a second adhesive layer is fixedly laminated on the second surface. As an example of the configuration of a double-sided adhesive sheet having such a substrate, in the single-sided adhesive sheet (1) shown in FIG. 1, the second surface (20B) of the supporting substrate (20) is a non-removable surface and a second adhesive layer is provided on the second surface (20B), the second surface of the second adhesive layer is bonded to the second surface (20B) of the supporting substrate (20), and the first surface of the second adhesive layer (a surface opposite to the second surface) is the second adhesive surface of the double-sided adhesive sheet having the substrate. The composition of the adhesive constituting the second adhesive layer may be the same as or different from the composition of the adhesive constituting the first adhesive layer. A double-sided adhesive sheet having a substrate before use may be in a form in which the first adhesive surface and the second adhesive surface are protected by a release liner, similar to the above-described double-sided adhesive sheet without a substrate.

[0026] Characteristics of the adhesive layer

[0027] (Refractive index)

[0028] The adhesive sheet disclosed herein has an adhesive layer having a refractive index greater than 1.570. Such an adhesive layer can be realized by forming at least one surface (adhesive surface) of said adhesive layer with an adhesive having a refractive index greater than 1.570. According to the technology disclosed herein, an adhesive having a refractive index greater than 1.570, an adhesive composition capable of forming said adhesive, and an adhesive sheet comprising said adhesive may be provided.

[0029] In addition, in this specification, the refractive index of an adhesive refers to the refractive index of the surface (adhesive surface) of the adhesive. The refractive index of the adhesive can be measured using a commercially available refractive index measuring device (Abbé refractive index meter) under conditions of a measurement wavelength of 589 nm and a measurement temperature of 25°C. As an Abé refractive index meter, for example, the "DR-M4" model manufactured by ATAGO or an equivalent product thereof is used. As a measurement sample, an adhesive layer consisting of the adhesive to be evaluated can be used. Specifically, the refractive index of the adhesive can be measured by the method described in the examples described below. The refractive index of the adhesive can be controlled, for example, by the composition of the adhesive (e.g., the composition of the monomer components constituting the base polymer, additives that may be used as needed, etc.).

[0030] In some embodiments, the refractive index of the adhesive may preferably be 1.580 or higher, more preferably 1.585 or higher, and even more preferably 1.590 or higher (e.g., 1.595 or higher). With an adhesive having such a refractive index, the behavior of light transmitted through the adhesive can be effectively controlled by utilizing the relationship between the relative refractive indices of the adhesive and the substrate. In some embodiments of the adhesive disclosed herein, the refractive index of the adhesive may be, for example, 1.600 or higher or greater than 1.600, 1.605 or higher or greater than 1.605, or 1.610 or higher or greater than 1.610. The preferred upper limit of the refractive index of the adhesive may vary depending on the refractive index of the substrate, etc., and is therefore not limited to a specific range. In some embodiments, considering the balance with adhesive properties and transparency, the refractive index of the adhesive may be, for example, 1.700 or less, 1.670 or less, or 1.650 or less.

[0031] In the case where the adhesive sheet disclosed herein is in the form of a double-sided adhesive sheet having one side as a first adhesive surface and the other side as a second adhesive surface (including both a double-sided adhesive sheet without a substrate and a double-sided adhesive sheet having a substrate; hereinafter the same unless specifically mentioned), at least the first adhesive surface must satisfy the refractive index of any of the above, and the refractive index of the second adhesive surface is not particularly limited.

[0032] In some embodiments, the refractive index n2 of the second adhesive surface may be approximately equal to the refractive index n1 of the first adhesive surface. More specifically, the absolute value of the difference between the refractive indices of the two adhesive surfaces, i.e., |n1-n2|, may be, for example, less than 0.05, or less than 0.03, or less than 0.01. The lower limit of |n1-n2| may be 0.00 or greater than 0.00. The relative relationship between the refractive indices of the two adhesive surfaces may be n1 > n2, and n1 <n2여도 되고, n1=n2여도 된다.

[0033] In several other embodiments, the difference between the refractive index n1 of the first adhesive surface of the adhesive sheet and the refractive index n2 of the second adhesive surface, i.e., n1-n2, may be, for example, greater than 0.00, greater than 0.01, greater than 0.03, greater than 0.05, greater than 0.10, greater than 0.15, greater than 0.20, or greater than 0.25. The relationship between n1 and n2 may be inverse. A double-sided adhesive sheet having different refractive indices on a first adhesive surface and a second adhesive surface can be realized, for example, by laminating first and second adhesive layers with different refractive indices onto a non-removable support substrate in a double-sided adhesive sheet having a substrate, or by making a double-sided adhesive sheet without a substrate into a laminated structure of two or more sub-adhesive layers and making the refractive index of the adhesive constituting the first adhesive surface and the refractive index of the adhesive constituting the second adhesive surface different from each other in the laminated structure.

[0034] (Total light transmittance)

[0035] The adhesive sheet disclosed herein has an adhesive layer having the high refractive index and an total light transmittance of 86% or more. An adhesive sheet having such a highly transparent adhesive layer can be preferably applied to applications requiring high light transmittance (e.g., optical applications) in configurations having or not having a substrate, or applications requiring performance that allows good visibility of an adherend through the adhesive sheet. In several embodiments, the total light transmittance of the adhesive layer is preferably 88% or more, more preferably 90% or more (e.g., greater than 90.0%), and may be 90.5% or more, 93% or more, or 95% or more. The upper limit of total light transmittance is, theoretically, the value obtained by subtracting light loss (Fresnel loss) due to reflection occurring at the air interface from 100%, and practically, it may be approximately 98% or less, approximately 96% or less, or approximately 95% or less. In some embodiments, considering the refractive index or adhesive properties, the total light transmittance of the adhesive layer may be approximately 94% or less, approximately 93% or less, or approximately 92% or less. The total light transmittance is measured using a commercially available transmittance meter in accordance with JIS K 7136:2000. As the transmittance meter, the product name "HAZEMETER HM-150" manufactured by Kijutsu Genkyujo of Shikisai Murakami or an equivalent product is used. More specifically, the total light transmittance of the adhesive layer can be measured according to the examples described below, for instance. The total light transmittance of the adhesive layer can be controlled, for example, by selecting the composition or thickness of the adhesive layer.

[0036] When the adhesive sheet disclosed herein is in the form of a double-sided adhesive sheet having a substrate in which a first adhesive layer and a second adhesive layer are fixedly laminated on a supporting substrate, at least the first adhesive layer must satisfy the total light transmittance of any of the above-described, and the total light transmittance of the second adhesive layer is not particularly limited. In a usage mode in which light escapes in the thickness direction of the adhesive sheet, it is preferable that the total light transmittance of the second adhesive layer satisfies any of the total light transmittances of the first adhesive layer described above. The relative relationship of the total light transmittances of the two adhesive layers may be such that the first adhesive layer > the second adhesive layer, the first adhesive layer < the second adhesive layer, or the first adhesive layer = the second adhesive layer.

[0037] (Haze value)

[0038] The adhesive sheet disclosed herein comprises an adhesive layer having the high refractive index and a haze value of 3.0% or less. In some embodiments, the haze value of the adhesive layer is preferably 2.0% or less, more preferably 1.0% or less, and even more preferably 0.9% or less. An adhesive sheet having such a highly transparent adhesive layer can be preferably applied to applications requiring high light transmittance (e.g., optical applications) in configurations having or not having a substrate, or to applications requiring performance that allows good visibility of an adherend through the adhesive sheet. In some embodiments, the haze value of the adhesive layer may be 0.8% or less, 0.5% or less, or 0.3% or less. The lower limit of the haze value of the adhesive layer is not particularly limited, and from the perspective of improving transparency, a smaller haze value is preferable. Meanwhile, in some embodiments, considering the refractive index or adhesive properties, the haze value may be, for example, 0.05% or more, 0.1% or more, 0.2% or more, 0.3% or more, or 0.4% or more. These haze values ​​for the adhesive layer may also preferably be applied to the haze value of the adhesive sheet when the technology disclosed herein is implemented in the form of a substrate-free adhesive sheet (typically, an adhesive sheet consisting of an adhesive layer).

[0039] Here, "haze value" refers to the ratio of diffuse transmitted light to total transmitted light when visible light is irradiated onto a measurement target. It is also called haze. The haze value can be expressed by the following formula.

[0040] Th(%)=Td / Tt×100

[0041] In the above formula, Th is the haze value (%), Td is the scattered light transmittance, and Tt is the total light transmittance. The haze value can be measured according to the method described in the examples to be described later. The haze value of the adhesive layer can be controlled, for example, by selecting the composition or thickness of the adhesive layer.

[0042] When the adhesive sheet disclosed herein is in the form of a double-sided adhesive sheet having a substrate in which a first adhesive layer and a second adhesive layer are fixedly laminated on a supporting substrate, at least the first adhesive layer needs to satisfy the haze value of any of the above-described values, and the haze value of the second adhesive layer is not particularly limited. In a usage mode in which light escapes in the thickness direction of the adhesive sheet, it is preferable that the haze value of the second adhesive layer satisfies any of the haze values ​​of the first adhesive layer described above. The relative relationship between the haze values ​​of the two adhesive layers may be the first adhesive layer > the second adhesive layer, the first adhesive layer < the second adhesive layer, or the first adhesive layer = the second adhesive layer.

[0043] (Surface smoothness of the adhesive surface)

[0044] In several embodiments of the adhesive sheet disclosed herein, the adhesive surface of the adhesive sheet preferably has high surface smoothness.

[0045] For example, it is preferable that the arithmetic mean illuminance Ra of the adhesive surface be limited to a predetermined value or less. A configuration having an adhesive surface designed to lower the arithmetic mean illuminance Ra is desirable from the perspective of optical homogeneity. By limiting the arithmetic mean illuminance Ra, for example, in a usage mode in which light is emitted through the adhesive surface (such as an adhesive sheet placed on the viewing side rather than a self-luminous element in a light-emitting device), it is possible to exert an effect of suppressing the occurrence of luminance non-uniformity caused by the surface condition of the adhesive layer. A low arithmetic mean illuminance Ra of the adhesive surface is also advantageous for suppressing optical distortion, and the suppression of optical distortion also contributes to the improvement of optical homogeneity. When the adhesive sheet disclosed herein is in the form of a double-sided adhesive sheet having a first adhesive surface and a second adhesive surface, it is preferable that the arithmetic mean illuminance Ra of at least the first adhesive surface be limited to a predetermined value or less, and it is more preferable that the arithmetic mean illuminance Ra of both adhesive surfaces be limited to a predetermined value or less. Since each adhesive surface of the double-sided adhesive sheet has high surface smoothness, it is possible to preferably achieve adhesion with excellent optical homogeneity.

[0046] In some embodiments, the arithmetic mean roughness Ra of the adhesive surface is preferably about 70 nm or less, more preferably about 65 nm or less, and even more preferably about 55 nm or less, and may be less than 50 nm, less than 45 nm, or less than 40 nm. In some embodiments, from the perspective of production efficiency, the arithmetic mean roughness Ra of the adhesive surface of the adhesive sheet may be, for example, about 10 nm or more, about 20 nm or more, or about 30 nm or more (for example, about 40 nm or more). In an embodiment where the adhesive sheet has a first adhesive surface and a second adhesive surface, the arithmetic mean roughness Ra of the first adhesive surface and the arithmetic mean roughness Ra of the second adhesive surface may be of the same degree or different.

[0047] In addition, for example, it is preferable that the maximum height Rz of the adhesive surface is limited to a predetermined value or less. A configuration having an adhesive surface designed to have a lower maximum height Rz is desirable from the perspective of optical homogeneity. By limiting the maximum height Rz, it is possible to exert an effect of suppressing the occurrence of luminance non-uniformity caused by the surface condition of the adhesive layer in a usage mode in which light is emitted through the adhesive surface as described above, for example. A low maximum height Rz of the adhesive surface is also advantageous for suppressing optical distortion. When the adhesive sheet disclosed herein is in the form of a double-sided adhesive sheet having a first adhesive surface and a second adhesive surface, it is preferable that the maximum height Rz of at least the first adhesive surface is limited to a predetermined value or less, and it is more preferable that the maximum height Rz of both adhesive surfaces is limited to a predetermined value or less. By having each adhesive surface of the double-sided adhesive sheet have high surface smoothness, adhesion with excellent optical homogeneity can be preferably realized.

[0048] In some embodiments, the maximum height Rz of the adhesive surface is preferably about 600 nm or less, more preferably about 500 nm or less, even more preferably about 450 nm or less, particularly preferably about 400 nm or less, and may be less than 350 nm, less than 300 nm, or less than 250 nm. In some embodiments, from the perspective of production efficiency, the maximum height Rz of the adhesive surface of the adhesive sheet may be, for example, about 10 nm or more, about 50 nm or more, about 100 nm or more, or about 200 nm or more. In an embodiment in which the adhesive sheet has a first adhesive surface and a second adhesive surface, the maximum height Rz of the first adhesive surface and the maximum height Rz of the second adhesive surface may be of the same degree or different.

[0049] The arithmetic mean roughness Ra and maximum height Rz of the adhesive surface are measured using a non-contact surface roughness measuring device. As a non-contact surface roughness measuring device, an optical interference type surface roughness measuring device is used, and for example, a 3D optical profiler (product name "NewView 7300", manufactured by ZYGO) or an equivalent product may be used. Specific measurement operations and measurement conditions can be set according to the measurement conditions described in the embodiments below, or so as to obtain results equivalent to or corresponding to those under said measurement conditions.

[0050] The arithmetic mean roughness Ra and maximum height Rz of the adhesive surface can be controlled by the composition or properties (viscosity, leveling properties, etc.) of the adhesive composition used to form the adhesive layer, the properties of the surface (release surface) of the release liner protecting the adhesive surface, etc.

[0051] (Absorption rate)

[0052] In several embodiments of the adhesive sheet disclosed herein, it is preferable that the adhesive layer constituting the adhesive sheet has an absorption rate limited to a predetermined value or less. For example, it is preferable that the refractive index, total light transmittance, and haze value described above be satisfied, and that the absorption rate is limited to a predetermined value or less. By limiting the absorption rate of the adhesive layer, dimensional changes in the adhesive layer caused by fluctuations in the amount of moisture within the adhesive layer (e.g., absorption and release of moisture such as humidity in the environment) tend to be suppressed. Accordingly, warping of the adhesive sheet or the substrate to which the adhesive sheet is attached can be suppressed due to a discrepancy in dimensional changes between the adhesive layer and the layer adjacent thereto (which may be a supporting substrate, a release liner, a substrate, etc.). Suppressing fluctuations in the amount of moisture within the adhesive layer is also desirable from the perspective of maintaining the flatness, transparency, refractive index, etc., of the adhesive layer at a constant level. In addition, since the adhesive layer with a low absorption rate is difficult to absorb moisture, it is suitable as an adhesive sheet used in components or products containing elements susceptible to moisture, such as organic EL devices.

[0053] In several embodiments, the absorption rate of the adhesive layer is preferably about 1.0% or less, preferably 0.7% or less, more preferably 0.5% or less (e.g., less than 0.5%), and may be 0.4% or less, 0.3% or less, or 0.2% or less. Although the lower limit of the absorption rate of the adhesive layer is not particularly limited, from a practical standpoint such as compatibility with adhesive properties, it may be, for example, 0.01% or more, 0.05% or more, 0.1% or more, 0.15% or more, or 0.25% or more. In the case where the adhesive sheet disclosed herein is in the form of a double-sided adhesive sheet having a substrate having a first adhesive layer and a second adhesive layer, it is preferable that the absorption rate of at least the first adhesive layer be limited to a predetermined value or less. From the perspective of achieving a higher effect, it is more desirable that the absorption rates of both the first and second adhesive layers be limited to below a predetermined value.

[0054] In addition, the absorption rate (also referred to as moisture content) of the adhesive layer is measured by the following method. The same method is employed in the embodiments described below.

[0055] [Measurement of Moisture Content]

[0056] The adhesive layer to be evaluated is cut to a size of 4 cm × 5 cm (area: 20 cm²) along with two release liners placed on one side and the other side, and the release liner on one side is removed and bonded to a pre-weighed aluminum foil. Next, the release liner on the other side of the adhesive layer is removed, and the sample is placed in a constant temperature and humidity bath at a temperature of 60°C and a relative humidity of 90%, and removed after 72 hours. After weighing the test specimen in which the adhesive layer and the aluminum foil are laminated, the moisture content is measured under the following conditions by the Karl Fischer total titration method using a moisture meter (Mitsubishi Kagaku Analytec CA-200 type) equipped with a heating vaporization device (Mitsubishi Kagaku Analytec VA-200 type).

[0057] Anode Fluid: Aquamicron AKX (Mitsubishi Kagaku)

[0058] Cathode fluid: Aquamicron CXU (Mitsubishi Chemical)

[0059] Heating / Vaporization Temperature: 150℃

[0060] (Gel fraction)

[0061] The gel fraction of the adhesive layer is appropriately set according to the purpose of use or mode of use, and is not limited to a specific range. The gel fraction is, for example, approximately 99% or less, and approximately 97% or less is suitable. From the perspective of facilitating a suitable combination of high refractive index and adhesive properties, in some preferred embodiments, the gel fraction may be approximately 95% or less, more preferably approximately 92% or less (for example, approximately 90% or less). It is also desirable that the gel fraction is not too high, from the perspective of properly following irregularities that may exist on the surface of the substrate (for example, irregular structures provided for the purpose of improving light extraction efficiency in a light-emitting device) and adhering well. In some embodiments, the gel fraction may be approximately 88% or less, approximately 75% or less, or approximately 65% ​​or less. In addition, regarding the perspective of imparting appropriate cohesiveness to the adhesive and properly expressing adhesive properties, the gel fraction of the adhesive layer is, for example, approximately 10% or more, approximately 20% or more, and may be approximately 30% or more. Regarding the resistance to deformation of the adhesive layer (such as preventing oozing due to pressure or bubbles caused by the incorporation of foreign substances), the gel fraction is preferably approximately 30% or more, more preferably approximately 40% or more, may be approximately 45% or more, may be approximately 50% or more, may be approximately 65% ​​or more, and may be approximately 75% or more. It is also preferable that the gel fraction of the adhesive sheet (typically an insubstantial adhesive sheet) be within the range exemplified above. The gel fraction can be controlled by the molecular weight, molecular structure, concentration, degree of crosslinking, etc. of the base polymer. The gel fraction is measured by the following method.

[0062] [Measurement of Gel Fraction]

[0063] A predetermined amount of adhesive sample (weight Wg1) is wrapped in a porous polytetrafluoroethylene membrane (weight Wg2) with an average pore diameter of 0.2㎛ in a dry-walled manner, and the opening is tied with a thread (weight Wg3). As the porous polytetrafluoroethylene (PTFE) membrane, the product name "Nittoplon (registered trademark) NTF1122" (average pore diameter 0.2㎛, porosity 75%, thickness 85㎛) available from Nitto Denko Co., Ltd. or an equivalent product is used.

[0064] The wrapped object is immersed in a sufficient amount of ethyl acetate and maintained at room temperature (typically 23°C) for 7 days to extract only the sol fraction of the adhesive to the outside of the film. Then, the wrapped object is removed, the ethyl acetate attached to the outer surface is wiped off, and the wrapped object is dried at 130°C for 2 hours to measure the weight (Wg4) of the wrapped object. The gel fraction of the adhesive layer is obtained by substituting each value into the following formula.

[0065] Gel fraction (%) = [(Wg4 - Wg2 - Wg3) / Wg1] × 100

[0066] When the adhesive sheet disclosed herein is in the form of a double-sided adhesive sheet having a first adhesive surface and a second adhesive surface, the gel fraction described above may be applied to at least the adhesive layer constituting the first adhesive surface, and preferably applied to both the adhesive layer constituting the first adhesive surface and the adhesive layer constituting the second adhesive surface. The gel fraction of the adhesive layer constituting the first adhesive surface and the gel fraction of the adhesive layer constituting the second adhesive surface may be of the same degree or may be different.

[0067] (Storage modulus G')

[0068] In the adhesive sheet disclosed herein, the storage modulus G' (hereinafter also referred to as "storage modulus G' (25)") of the adhesive constituting the adhesive layer at 25°C is appropriately set according to the purpose of use or mode of use, and is not limited to a specific range. The storage modulus G' (25) of the adhesive may be, for example, approximately 700 kPa or less. In several embodiments, from the perspective of ease of attachment to a substrate, the storage modulus G' (25) of the adhesive is advantageous to be approximately 600 kPa or less, preferably 500 kPa or less, and more preferably 400 kPa or less (for example, 350 kPa or less). In some embodiments, from the perspective of increasing the flexibility of the adhesive in the room temperature range (e.g., 25°C) to make it easier to adhere to the substrate, the storage modulus G' (25) of the adhesive is advantageous to be approximately 330 kPa or less, and preferably 300 kPa or less. In some embodiments where adhesion or flexibility in the room temperature range is more important, the storage modulus G' (25) of the adhesive may be, for example, less than 270 kPa or less than 250 kPa, and it is advantageous to be less than 200 kPa, preferably less than 180 kPa, and more preferably less than 160 kPa (e.g., less than 140 kPa). In some embodiments, the storage modulus G' (25) of the adhesive may be less than 100 kPa or less than 90 kPa. The lower limit of the storage modulus G' (25) of the adhesive is not specifically limited, but from the perspective of processability or handling, it may be, for example, 30 kPa or more, 50 kPa or more, or 70 kPa or more. In some embodiments, considering the high refractive index, the storage modulus G' (25) may be 100 kPa or more, 150 kPa or more, 200 kPa or more, 250 kPa or more, or 300 kPa or more.

[0069] In the adhesive sheet disclosed herein, the storage modulus G' (hereinafter also referred to as "storage modulus G' (50)") of the adhesive constituting the adhesive layer at 50°C is not particularly limited and may be, for example, less than 100 kPa. In several embodiments, the storage modulus G' (50) is suitable to be less than 60 kPa, preferably less than 40 kPa, and more preferably less than 38 kPa (for example, less than 36 kPa). An adhesive with such a limited storage modulus G' (50) can easily increase its adhesion to a substrate by applying appropriate heating as needed, thereby improving its adhesion to the substrate. The lower limit of the storage modulus G' (50) of the adhesive is not particularly limited. In some embodiments, regarding the heat resistance properties of the adhesive, the storage modulus G' (50) may be, for example, 10 kPa or more, 15 kPa or more, 20 kPa or more, or 23 kPa or more.

[0070] In several embodiments of the adhesive sheet disclosed herein, the adhesive constituting the adhesive layer is under the following conditions:

[0071] (a) a storage modulus G' (25) at 25°C of 350 kPa or less (preferably less than 200 kPa, e.g. 180 kPa or less); and

[0072] (b) a storage modulus G'(50) at 50°C of less than 60 kPa (preferably less than 50 kPa, more preferably less than 40 kPa, for example less than 38 kPa);

[0073] It is desirable to satisfy at least one of the above conditions. An adhesive that satisfies at least condition (a) is desirable in terms of adhesion to a substrate at room temperature (e.g., 25°C). An adhesive that satisfies at least condition (b) is desirable because its adhesion to a substrate can be easily improved by heating it to a temperature slightly higher than room temperature. An adhesive that does not satisfy condition (a) but satisfies (b) can be used as a heat-activated type adhesive, which has good reworkability (re-adhesion) at the beginning of application at room temperature and can effectively increase the peel strength from the substrate by heating it to a temperature slightly higher than room temperature. The heat activation may be performed by heating the adhesive to a temperature slightly higher than room temperature when applying it to a substrate. The temperature slightly higher than the above room temperature is, for example, about 60°C or lower, and preferably about 55°C or lower (for example, about 50°C or lower).

[0074] In some embodiments of the adhesive sheet disclosed herein, the ratio of the storage modulus G'(50)[kPa] to the storage modulus G'(25)[kPa] of the adhesive constituting the adhesive layer, i.e., the storage modulus ratio G'(50) / G'(25), may be, for example, 70% or less, 40% or less, 30% or less, or 20% or less. An adhesive with a low G'(50) / G'(25) is suitable for use as a heat-activated type adhesive. The lower limit of G'(50) / G'(25) is not particularly limited. G'(50) / G'(25) is, for example, 5% or more, and is preferably 10% or more from the perspective of the heat resistance properties of the adhesive, and may be 12% or more, or 15% or more.

[0075] Storage modulus G' (25) and G' (50) can be obtained by dynamic viscoelasticity measurement, and G' (50) / G' (25) can be calculated from the result. Dynamic viscoelasticity measurement can be performed by the standard method using a commercially available dynamic viscoelasticity measuring device, for example, using the "Advanced Rheometric Expansion System (ARES)" manufactured by TA Instruments or an equivalent product, and can be performed under the following measurement conditions. As a sample for measurement, a thickness of about 1.5 mm is prepared by laminating the adhesive layer to be evaluated as needed.

[0076] [Measurement Conditions]

[0077] Transformation Mode: Twist

[0078] Measurement frequency: 1Hz

[0079] Heating rate: 5℃ / min

[0080] Shape: Parallel plate 7.9 mm φ

[0081] The storage modulus G' (25), G' (50), and storage modulus ratio of the adhesive layer can be controlled by the selection of the composition of the monomer components constituting the base polymer of the adhesive (e.g., the selection of the type and content of monomer (m1)), the selection of whether or not to use a crosslinking agent, the selection of its type and amount, and the selection of whether or not to use a refractive index improver or plasticizing material described later, the selection of its type and amount. For example, as monomer (m1), by using a relatively small amount of a second monomer with a different chemical structure from the first monomer in combination with the first monomer, in addition to the first monomer which is the main component of the monomer (m1), G' (50) can be reduced in addition to the case where the first monomer is used alone as monomer (m1), thereby lowering G' (50) / G' (25).

[0082] When the adhesive sheet disclosed herein is in the form of a double-sided adhesive sheet having a first adhesive surface and a second adhesive surface (e.g., a double-sided adhesive sheet having a substrate having a first adhesive layer and a second adhesive layer, a substrate-free double-sided adhesive sheet in which a sub-adhesive layer constituting the first adhesive surface and a sub-adhesive layer constituting the second adhesive surface are laminated without passing through a non-adhesive substrate, etc., the same applies to other similar substrates), the above-described storage modulus G' (25), G' (50), and storage modulus ratio are applied to at least the adhesive layer constituting the first adhesive surface, and preferably to both the adhesive layer constituting the first adhesive surface and the adhesive layer constituting the second adhesive surface. The storage modulus G' of the adhesive layer constituting the first adhesive surface and the storage modulus G' of the adhesive layer constituting the second adhesive surface may be of the same degree or may be different.

[0083] In some embodiments of the technology disclosed herein, the peak temperature of tanδ of the adhesive constituting the adhesive layer is preferably approximately -50°C or higher, and also preferably approximately 50°C or lower. Here, tanδ (loss tangent) of the adhesive refers to the ratio of the loss modulus G" to the storage modulus G' of the adhesive. That is, tanδ = G" / G'. The tanδ of the adhesive is obtained by placing a disc-shaped adhesive sample with a thickness of approximately 2 mm and a diameter of 7.9 mm between parallel plates, applying shear deformation at a frequency of 1 Hz using a viscoelastic testing device, performing a temperature dispersion test of the adhesive in a shear mode under conditions of a measurement temperature range of -60°C to 60°C and a heating rate of 5°C / min, and using the storage modulus G' (Pa) and loss modulus G" (Pa) at that time, by the following equation: tanδ = G" / G'; From the trend of tanδ in the above temperature range, the peak temperature of tanδ of the adhesive (hereinafter referred to as Tpeak) is obtained. As a viscoelasticity test device, ARES manufactured by TA Instruments or an equivalent product thereof may be used.

[0084] In some embodiments, the Tpeak of the adhesive is advantageous to be 45°C or lower or 35°C or lower, and is preferably 30°C or lower (e.g., 25°C or lower), and may be 20°C or lower or 15°C or lower. With adhesives having a lower Tpeak, it tends to be easier to obtain good initial adhesion or bonding properties in the room temperature range. On the other hand, not having a Tpeak of the adhesive that is too low is desirable from the perspective of imparting appropriate cohesiveness to the adhesive and tends to be suitable for compatibility with high refractive index. In this regard, in some embodiments, the Tpeak of the adhesive may be, for example, -40°C or higher, -30°C or higher, -20°C or higher, -5°C or higher, 5°C or higher, 15°C or higher, and furthermore, 25°C or higher. An adhesive with a relatively high Tpeak can be preferably used in a manner where, when attaching to a substrate, either one or both of the adhesive and the substrate are heated to a temperature slightly higher than room temperature as needed. The Tpeak of the adhesive can be controlled by selecting the composition of the adhesive (e.g., the composition of the monomer components constituting the base polymer, the presence or absence of refractive index improvers or plasticizing materials, and the selection of their types and amounts).

[0085] When the adhesive sheet disclosed herein is in the form of a double-sided adhesive sheet having a first adhesive surface and a second adhesive surface, the Tpeak of the adhesive described above is preferably applied to at least the adhesive layer constituting the first adhesive surface, and more preferably to both the adhesive layer constituting the first adhesive surface and the adhesive layer constituting the second adhesive surface. The Tpeak of the adhesive layer constituting the first adhesive surface and the Tpeak of the adhesive layer constituting the second adhesive surface may be of the same degree or different.

[0086] <Adhesive layer>

[0087] (Base polymer)

[0088] In the technology disclosed herein, the type of adhesive constituting the adhesive layer is not particularly limited. The adhesive may include one or more types of various rubbery polymers that can be used in the field of adhesives, such as acrylic polymers, rubber polymers (e.g., natural rubber, synthetic rubber, mixtures thereof), polyester polymers, urethane polymers, polyether polymers, silicone polymers, polyamide polymers, and fluorine polymers, as an adhesive polymer (hereinafter also referred to as a "base polymer" in the sense of a structural polymer that forms the adhesive). From the perspective of adhesive performance or cost, an adhesive containing an acrylic polymer or a rubber polymer as a base polymer may be preferably adopted. Among these, an adhesive having an acrylic polymer as the base polymer (acrylic adhesive) is preferred. The technology disclosed herein is preferably implemented in a manner using an acrylic adhesive.

[0089] Hereinafter, we will mainly describe an adhesive layer composed of an acrylic adhesive, that is, an adhesive sheet having an acrylic adhesive layer; however, it is not intended to limit the adhesive layer of the adhesive sheet disclosed herein to one composed of an acrylic adhesive.

[0090] In addition, in this specification, the term "base polymer" of an adhesive refers to the main component of a rubbery polymer included in the adhesive, and is not interpreted in any limiting way other than this. The above rubbery polymer refers to a polymer that exhibits rubbery elasticity in the temperature range near room temperature. In addition, in this specification, the term "main component" refers to a component included in an amount exceeding 50 weight% unless otherwise specified.

[0091] In addition, in this specification, the term "acrylic polymer" refers to a polymer comprising monomer units derived from a monomer having at least one (meth)acryloyl group in one molecule as monomer units constituting the said polymer. Hereinafter, a monomer having at least one (meth)acryloyl group in one molecule is also referred to as an "acrylic monomer." Accordingly, an acrylic polymer in this specification is defined as a polymer comprising monomer units derived from an acrylic monomer. As a typical example of an acrylic polymer, a polymer in which the proportion of acrylic monomers among the total monomers used in the synthesis of the said acrylic polymer is greater than 50 weight% (preferably greater than 70 weight%, for example greater than 90 weight%) may be cited.

[0092] Furthermore, in this specification, the term "(meth)acryloyl" refers comprehensively to acryloyl and methacryloyl. Likewise, the term "(meth)acrylate" refers comprehensively to acrylate and methacrylate, and the term "(meth)acryl" refers comprehensively to acryl and methacryl, respectively. Accordingly, the concept of acrylic monomers referred to herein may include both monomers having an acryloyl group (acrylic monomers) and monomers having a methacryloyl group (methacrylic monomers).

[0093] (Acrylic polymer(A))

[0094] The adhesive sheet disclosed herein may preferably be implemented in an embodiment comprising an acrylic adhesive layer having a refractive index greater than 1.570, a total light transmittance of 86% or more, and a haze value of 3.0% or less (preferably 2.0% or less, more preferably 1.0% or less). As for the acrylic polymer that serves as the base polymer of the acrylic adhesive layer, it is preferable to include an aromatic ring-containing monomer (m1) as a monomer component constituting the acrylic polymer. That is, an acrylic polymer containing an aromatic ring-containing monomer (m1) as a monomer unit is preferred. Hereinafter, such an acrylic polymer is also referred to as "acrylic polymer (A)". In this specification, the term "monomer component constituting an acrylic polymer" refers to a monomer constituting a repeating unit of an acrylic polymer in an adhesive formed from said adhesive composition, regardless of whether it is included in the adhesive composition in the form of a pre-formed polymer (which may be an oligomer) or in the adhesive composition in the form of an unpolymerized monomer. That is, the monomer component constituting an acrylic polymer may be included in the adhesive composition in any of the forms of a polymer, an unpolymerized polymer, or a partial polymer. From the perspective of ease of preparation of the adhesive composition, etc., in several embodiments, an adhesive composition is preferred in which substantially all of the monomer component (e.g., 95% by weight or more, preferably 99% by weight or more) is included in the form of a polymer. An adhesive composition in which substantially all of the monomer component is included in the form of a polymer is also preferred from the perspective that it is easy to form an adhesive sheet with minimal deformation or warping.

[0095] (Monomer(m1))

[0096] As the monomer (m1), a compound comprising at least one aromatic ring and at least one ethylenically unsaturated group in one molecule is used. As the monomer (m1), one of these compounds may be used alone or in combination of two or more.

[0097] Examples of the above ethylenically unsaturated groups include (meth)acryloyl groups, vinyl groups, (meth)allyl groups, etc. (meth)acryloyl groups are preferred from the perspective of polymerization reactivity, and acryloyl groups are more preferred from the perspective of flexibility or tackiness. In order to suppress the reduction of flexibility of the adhesive, a compound having one ethylenically unsaturated group (i.e., a monofunctional monomer) is preferably used as the monomer (m1).

[0098] The number of aromatic rings included in one molecule of the compound used as monomer (m1) may be 1 or 2 or more. The upper limit of the number of aromatic rings included in the monomer (m1) is not particularly limited and may be, for example, 16 or less. In several embodiments, from the perspective of ease of preparation of the acrylic polymer (A) or transparency of the adhesive, the number of aromatic rings may be, for example, 12 or less, preferably 8 or less, more preferably 6 or less, 5 or less, 4 or less, 3 or less, or 2 or less.

[0099] The aromatic ring of the compound used as the monomer (m1) may be a carbon ring, for example, a benzene ring (which may be a benzene ring constituting part of a biphenyl structure or a fluorene structure); a condensed ring of a naphthalene ring, an indene ring, an azulene ring, anthracene ring, or a phenanthrene ring; or it may be a complex ring, for example, a pyridine ring, a pyrimidine ring, a pyridazine ring, a pyrazine ring, a triazine ring, a pyrrole ring, a pyrazol ring, an imidazole ring, a triazole ring, an oxazole ring, an isooxazole ring, a thiazole ring, or a thiophene ring. In the complex ring, the heteroatoms included as ring constituent atoms may be one or more selected from the group consisting of nitrogen, sulfur, and oxygen, for example. In some embodiments, the heteroatoms constituting the complex ring may be one or both of nitrogen and sulfur. The monomer (m1) may have a structure in which one or more carbon rings and one or more complex rings are condensed, for example, such as the dinaphthorthiophene structure.

[0100] The above-mentioned aromatic ring (preferably a carbon ring) may have one or more substituents on the ring constituent atoms, or it may not have any substituents. When having substituents, examples of such substituents include, but are not limited to, alkyl groups, alkoxy groups, aryloxy groups, hydroxyl groups, hydroxyloxy groups, glycidyloxy groups, etc. In the case of substituents containing carbon atoms, the number of carbon atoms included in the substituent is preferably 1 to 4, more preferably 1 to 3, and may be, for example, 1 or 2. In some embodiments, the above-mentioned aromatic ring may not have substituents on the ring constituent atoms, or may be an aromatic ring having one or more substituents selected from the group consisting of alkyl groups, alkoxy groups, and halogen atoms (e.g., bromine atoms). In addition, the statement that the aromatic ring of the monomer (m1) has a substituent on the ring constituent atom means that the aromatic ring has a substituent other than a substituent having an ethylenically unsaturated group.

[0101] The aromatic ring and the ethylenically unsaturated group may be directly bonded or bonded through a linking group. The linking group may be a group comprising one or more structures selected from, for example, alkylene groups, oxyalkylene groups, poly(oxyalkylene) groups, phenyl groups, alkylphenyl groups, alkoxyphenyl groups, groups having a structure in which one or more hydrogen atoms in these groups are substituted with hydroxyl groups (e.g., hydroxyalkylene groups), oxy groups (-O- groups), thiooxy groups (-S- groups), etc. In some embodiments, an aromatic ring-containing monomer having a structure in which the aromatic ring and the ethylenically unsaturated group are directly bonded or bonded through a linking group selected from the group consisting of alkylene groups, oxyalkylene groups, and poly(oxyalkylene) groups may be preferably employed. The number of carbon atoms in the above alkylene group and the above oxyalkylene group is preferably 1 to 4, more preferably 1 to 3, and may be, for example, 1 or 2. The number of repetitions of the oxyalkylene unit in the above poly(oxyalkylene) group may be, for example, 2 to 3.

[0102] Examples of compounds that can be preferably employed as monomers (m1) include aromatic ring-containing (meth)acrylates and aromatic ring-containing vinyl compounds. Aromatic ring-containing (meth)acrylates and aromatic ring-containing vinyl compounds may each be used individually or in combination of two or more types. One or more aromatic ring-containing (meth)acrylates and one or more aromatic ring-containing vinyl compounds may also be used in combination.

[0103] The content of monomer (m1) in the monomer component constituting the acrylic polymer (A) is not particularly limited and can be set to realize an adhesive layer that is compatible with the desired refractive index and adhesive properties (e.g., peel strength, flexibility, etc.) and / or optical properties (e.g., total light transmittance, haze value, etc.). In some embodiments, the content of monomer (m1) in the monomer component may be, for example, 30 weight% or more, preferably 50 weight% or more, 60 weight% or more, or 70 weight% or more. In some preferred embodiments, from the viewpoint of making it easier to obtain a higher refractive index, the content of monomer (m1) may be, for example, more than 70 weight%, 75 weight% or more, 80 weight% or more, 85 weight% or more, 90 weight% or more, or 95 weight% or more. The upper limit of the content of monomer (m1) in the above monomer component is 100% by weight. From the perspective of achieving a good balance between high refractive index and adhesive properties and / or optical properties, it is advantageous to keep the content of the above monomer (m1) less than 100% by weight; for example, it is preferable to be approximately 99% by weight or less, more preferable to be 98% by weight or less, and it may be 97% by weight or less, or 96% by weight or less. In some embodiments, the content of the above monomer (m1) may be 93% by weight or less, 90% by weight or less, 80% by weight or less, or 75% by weight or less. In some embodiments where adhesive properties and / or optical properties are given more importance, the content of the above monomer (m1) in the above monomer component may be 70% by weight or less, 60% by weight or less, or 45% by weight or less.

[0104] In several aspects of the technology disclosed herein, as the monomer (m1), a monomer having two or more aromatic rings (preferably carbon rings) in one molecule may be preferably employed, as it is easy to obtain a high refractive index effect. Examples of a monomer having two or more aromatic rings in one molecule (hereinafter also referred to as a "monomer containing multiple aromatic rings") include a monomer having a structure in which two or more non-condensing aromatic rings are bonded through a linking group, a monomer having a structure in which two or more non-condensing aromatic rings are chemically bonded directly (i.e., without passing through other atoms), a monomer having a condensed aromatic ring structure, a monomer having a fluorene structure, a monomer having a dinaphthiophene structure, a monomer having a dibenzothiophene structure, etc. Monomers containing multiple aromatic rings may be used as a single type or in combination of two or more types.

[0105] The above linking group is, for example, an oxy group (-O-), a thiooxy group (-S-), an oxyalkylene group (e.g., -O-(CH2) n - group, where n is 1 to 3, preferably 1), thiooxyalkylene group (e.g., -S-(CH2) n - group, where n is 1 to 3, preferably 1), straight-chain alkylene group (i.e., -(CH2) n - group, where n is 1 to 6, preferably 1 to 3), the alkylene group in the oxyalkylene group, the thiooxyalkylene group, and the straight-chain alkylene group may be a group in which the alkylene group is partially halogenated or fully halogenated. Suitable examples of the linking group for the flexibility of the adhesive include oxy groups, thiooxy groups, oxyalkylene groups, and straight-chain alkylene groups. Specific examples of monomers having a structure in which two or more non-condensing aromatic rings are bonded through a linking group include phenoxybenzyl (meth)acrylate (e.g., m-phenoxybenzyl (meth)acrylate), thiophenoxybenzyl (meth)acrylate, benzylbenzyl (meth)acrylate, etc.

[0106] Monomers having a structure in which two or more non-condensing aromatic rings are directly chemically bonded may be, for example, biphenyl structure-containing (meth)acrylates, triphenyl structure-containing (meth)acrylates, vinyl group-containing biphenyls, etc. Specific examples include o-phenylphenol (meth)acrylates, biphenylmethyl (meth)acrylates, etc.

[0107] Examples of monomers having the above-mentioned condensed aromatic ring structure include naphthalene ring-containing (meth)acrylate, anthracene ring-containing (meth)acrylate, vinyl group-containing naphthalene, vinyl group-containing anthracene, etc. Specific examples include 1-naphthylmethyl(meth)acrylate (alias: 1-naphthalenemethyl(meth)acrylate), hydroxyethylated β-naphthol acrylate, 2-naphthoethyl(meth)acrylate, 2-naphthoxyethyl acrylate, 2-(4-methoxy-1-naphthoxy)ethyl(meth)acrylate, etc.

[0108] Specific examples of monomers having the above-mentioned fluorene structure include 9,9-bis(4-hydroxyphenyl)fluorene(meth)acrylate and 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene(meth)acrylate. In addition, since monomers having the above-mentioned fluorene structure include a structural portion in which two benzene rings are directly chemically bonded, they are included in the concept of monomers having a structure in which two or more non-condensing aromatic rings are directly chemically bonded.

[0109] Examples of monomers having the above-mentioned dinaphthothiophen structure include (meth)acryloyl group-containing dinaphthiophen, vinyl group-containing dinaphthiophen, (meth)allyl group-containing dinaphthiophen, etc. As a specific example, (meth)acryloyloxymethyldinaphthiophen (e.g., CH2CH(R) at the 5 or 6 position of the dinaphthiophen ring 1 A compound having a structure in which )C(O)OCH2- is bonded. Here, R 1(is a hydrogen atom or a methyl group), (meth)acryloyloxyethyldinaphthiophen (e.g., at the 5 or 6 position of the dinaphthiophen ring, CH2CH(R 1 )C(O)OCH(CH3)- or CH2CH(R 1 A compound having a structure in which )C(O)OCH2CH2- is bonded. Here, R 1 Examples include (which is a hydrogen atom or a methyl group), vinyldinaphthiophene (e.g., a compound with a structure in which a vinyl group is bonded to the 5th or 6th position of a naphthiophene ring), (meth)allyloxydinaphthiophene, etc. In addition, monomers having a dinaphthiophene structure are included in the concept of monomers having a condensed aromatic ring structure by including a naphthalene structure, or by having a structure in which a thiophene ring and two naphthalene structures are condensed.

[0110] Examples of monomers having the above dibenzothiophene structure include (meth)acryloyl group-containing dibenzothiophene and vinyl group-containing dibenzothiophene. In addition, monomers having the dibenzothiophene structure are included in the concept of monomers having the above condensed aromatic ring structure in that they have a structure in which a thiophene ring and two benzene rings are condensed.

[0111] In addition, the dinaphthorthiophene structure and the dibenzothiophene structure do not correspond to a structure in which two or more non-condensed aromatic rings are directly chemically bonded.

[0112] As the monomer (m1) in the technology disclosed herein, a monomer having one aromatic ring (preferably a carbon ring) per molecule may be used. A monomer having one aromatic ring per molecule can be helpful, for example, in improving the flexibility of the adhesive, adjusting adhesive properties, or improving transparency. In several embodiments, a monomer having one aromatic ring per molecule is preferably used in combination with a monomer containing multiple aromatic rings from the perspective of improving the refractive index of the adhesive.

[0113] Examples of monomers having one aromatic ring in one molecule include carbon aromatic ring-containing (meth)acrylates such as benzyl (meth)acrylate, methoxybenzyl (meth)acrylate, phenyl (meth)acrylate, ethoxylated phenol (meth)acrylate, phenoxypropyl (meth)acrylate, phenoxybutyl (meth)acrylate, cresyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, chlorobenzyl (meth)acrylate, etc.; Bromine-substituted aromatic ring-containing (meth)acrylates, such as 2-(4,6-dibromo-2-s-butylphenoxy)ethyl (meth)acrylate, 2-(4,6-dibromo-2-isopropylphenoxy)ethyl (meth)acrylate, 6-(4,6-dibromo-2-s-butylphenoxy)hexyl (meth)acrylate, 6-(4,6-dibromo-2-isopropylphenoxy)hexyl (meth)acrylate, 2,6-dibromo-4-nonylphenylacrylate, 2,6-dibromo-4-dodecylphenylacrylate; carbon aromatic ring-containing vinyl compounds, such as styrene, α-methylstyrene, vinyltoluene, tert-butylstyrene; Examples include compounds having vinyl substituents on a complex aromatic ring, such as N-vinylpyridine, N-vinylpyrimidine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, etc.

[0114] As the monomer (m1), a monomer having a structure in which an oxyethylene chain is interposed between the ethylenically unsaturated group and the aromatic ring in the various aromatic ring-containing monomers described above may be used. A monomer in which an oxyethylene chain is interposed between the ethylenically unsaturated group and the aromatic ring in this way can be identified as an ethoxylated form of the original monomer. The number of repetitions of the oxyethylene unit (-CH2CH2O-) in the oxyethylene chain is typically 1 to 4, preferably 1 to 3, more preferably 1 to 2, and for example, 1. Specific examples of the ethoxylated aromatic ring-containing monomer include ethoxylated o-phenylphenol (meth)acrylate, ethoxylated nonylphenol (meth)acrylate, ethoxylated cresol (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol di(meth)acrylate, etc.

[0115] The content of the monomer containing multiple aromatic rings in the monomer (m1) is not particularly limited and, for example, may be 5% by weight or more, 25% by weight or more, or 40% by weight or more. In some embodiments, from the viewpoint of making it easier to realize an adhesive having a higher refractive index, the content of the monomer containing multiple aromatic rings in the monomer (m1) may, for example, be 50% by weight or more, preferably 70% by weight or more, 85% by weight or more, 90% by weight or more, or 95% by weight or more. Substantially 100% by weight of the monomer (m1) may be the monomer containing multiple aromatic rings. That is, only one or two or more types of monomers containing multiple aromatic rings may be used as the monomer (m1). In addition, in several embodiments, for example, considering the balance between high refractive index and adhesive properties and / or optical properties, the content of the monomer containing multiple aromatic rings in the monomer (m1) may be less than 100 wt%, 98 wt% or less, 90 wt% or less, 80 wt% or less, or 65 wt% or less. In several embodiments, considering adhesive properties and / or optical properties, the content of the monomer containing multiple aromatic rings in the monomer (m1) may be 70 wt% or less, 50 wt% or less, 25 wt% or less, or 10 wt% or less. The technology disclosed herein may also be implemented in an embodiment where the content of the monomer containing multiple aromatic rings in the monomer (m1) is less than 5 wt%. A monomer containing multiple aromatic rings may not be used.

[0116] The content of the monomer containing multiple aromatic rings in the monomer component constituting the acrylic polymer is not particularly limited and can be set to realize an adhesive layer that achieves compatibility with the desired refractive index and adhesive properties (e.g., peel strength, flexibility, etc.) and / or optical properties (e.g., total light transmittance, haze value, etc.). The content of the monomer containing multiple aromatic rings in the monomer component may, for example, be 3 weight% or more, 10 weight% or more, or 25 weight% or more. In several embodiments, from the viewpoint of making it easier to realize an adhesive having a higher refractive index, the content of the monomer containing multiple aromatic rings in the monomer component may, for example, exceed 35 weight%, preferably exceed 50 weight%, exceed 70 weight%, 75 weight% or more, 85 weight% or more, 90 weight% or more, or 95 weight% or more. The content of the monomer containing multiple aromatic rings in the above monomer component may be 100% by weight, but from the perspective of achieving a good balance between high refractive index and adhesive properties and / or optical properties, it is advantageous to keep it less than 100% by weight, preferably about 99% by weight or less, more preferably 98% by weight or less, and may be 96% by weight or less, 93% by weight or less, 90% by weight or less, 85% by weight or less, 80% by weight or less, or 75% by weight or less. In several embodiments, considering adhesive properties and / or optical properties, the content of the monomer containing multiple aromatic rings in the above monomer component may be 70% by weight or less, 50% by weight or less, 25% by weight or less, 15% by weight or less, or 5% by weight or less. The technology disclosed herein may also be implemented in an embodiment in which the content of the monomer containing multiple aromatic rings in the monomer component is less than 3 weight percent.

[0117] In several embodiments of the technology disclosed herein, a high-refractive-index monomer may preferably be employed as at least a portion of the monomer (m1). Here, "high-refractive-index monomer" refers to a monomer whose refractive index is, for example, approximately 1.510 or higher, preferably approximately 1.530 or higher, and more preferably approximately 1.550 or higher. Although the upper limit of the refractive index of the high-refractive-index monomer is not particularly limited, from the perspective of ease of preparation of the adhesive composition and ease of compatibility with flexibility suitable for the adhesive, for example, it may be 3.000 or lower, 2.500 or lower, 2.000 or lower, 1.900 or lower, 1.800 or lower, or 1.700 or lower. The high-refractive-index monomer may be used as a single type or in combination of two or more types.

[0118] In addition, the refractive index of the monomer is measured using an Abbe refractive index meter under conditions of a measurement wavelength of 589 nm and a measurement temperature of 25°C. As the Abbe refractive index meter, the ATAGO model "DR-M4" or an equivalent product may be used. If the nominal value of the refractive index at 25°C is provided by the manufacturer, that nominal value may be adopted.

[0119] As the above high-refractive-index monomer, a compound having a corresponding refractive index can be appropriately adopted from among compounds included in the concept of the aromatic ring-containing monomer (m1) disclosed herein (e.g., compounds and groups of compounds exemplified above). Specific examples include m-phenoxybenzyl acrylate (refractive index: 1.566, Tg of homopolymer: -35°C), 1-naphthylmethyl acrylate (refractive index: 1.595, Tg of homopolymer: 31°C), ethoxylated o-phenylphenol acrylate (number of repeating oxyethylene units: 1, refractive index: 1.578), benzyl acrylate (refractive index (nD20): 1.519, Tg of homopolymer: 6°C), phenoxyethyl acrylate (refractive index (nD20): 1.517, Tg of homopolymer: 2°C), phenoxydiethylene glycol acrylate (refractive index: 1.510, Tg of homopolymer: -35°C), and 6-acryloyloxymethyldinaftothiophene (6MDNTA, refractive index: Examples include 6-methacryloyloxymethyldinaphthothiophen (6MDNTMA, refractive index: 1.75), 5-acryloyloxyethyldinaphthothiophen (5EDNTA, refractive index: 1.786), 6-acryloyloxyethyldinaphthothiophen (6EDNTA, refractive index: 1.722), 6-vinyldinaphthothiophen (6VDNT, refractive index: 1.802), and 5-vinyldinaphthothiophen (abbreviation: 5VDNT, refractive index: 1.793), but are not limited to these.

[0120] The content of the high refractive index monomer (i.e., an aromatic ring-containing monomer having a refractive index of approximately 1.510 or higher, preferably approximately 1.530 or higher, more preferably approximately 1.550 or higher) in the monomer (m1) is not particularly limited and, for example, may be 5 weight% or higher, 25 weight% or higher, 35 weight% or higher, or 40 weight% or higher. In some embodiments, from the viewpoint of making it easier to obtain a higher refractive index, the content of the high refractive index monomer in the monomer (m1) may be, for example, 50 weight% or higher, preferably 70 weight% or higher, 85 weight% or higher, 90 weight% or higher, or 95 weight% or higher. Substantially 100 weight% of the monomer (m1) may be the high refractive index monomer. In addition, in several embodiments, for example, with respect to achieving a good balance between high refractive index and adhesive properties and / or optical properties, the content of the high refractive index monomer in the monomer (m1) may be less than 100 wt%, 98 wt% or less, 90 wt% or less, 80 wt% or less, or 65 wt% or less. In several embodiments, considering adhesive properties and / or optical properties, the content of the high refractive index monomer in the monomer (m1) may be 70 wt% or less, 50 wt% or less, 25 wt% or less, 15 wt% or less, or 10 wt% or less. The technology disclosed herein may also be implemented in an embodiment where the content of the high refractive index monomer in the monomer component (m1) is less than 5 wt%. It is not necessary to use a high refractive index monomer.

[0121] The content of the high-refractive-index monomer in the monomer component constituting the acrylic polymer is not particularly limited and can be set to realize an adhesive layer that is compatible with the desired refractive index and adhesive properties (e.g., peel strength, flexibility, etc.) and / or optical properties (e.g., total light transmittance, haze value, etc.). The content of the high-refractive-index monomer in the monomer component may be, for example, 3 weight% or more, 10 weight% or more, or 25 weight% or more. In several embodiments, from the viewpoint of making it easier to realize an adhesive having a higher refractive index, the content of the high-refractive-index monomer in the monomer component may be, for example, greater than 35 weight%, preferably greater than 50 weight%, greater than 70 weight%, 75 weight% or more, 85 weight% or more, 90 weight% or more, or 95 weight% or more. The content of the high-refractive-index monomer in the above monomer component may be 100% by weight, but from the perspective of achieving a good balance between the high-refractive-index and adhesive properties and / or optical properties, it is advantageous to keep it less than 100% by weight, preferably 99% by weight or less, more preferably 98% by weight or less, and may be 96% by weight or less, 93% by weight or less, 90% by weight or less, 85% by weight or less, 80% by weight or less, or 75% by weight or less. In several embodiments, considering the adhesive properties and / or optical properties, the content of the high-refractive-index monomer in the above monomer component may be 70% by weight or less, 50% by weight or less, 25% by weight or less, 15% by weight or less, or 5% by weight or less. The technology disclosed herein may also be implemented in an embodiment in which the content of the high-refractive-index monomer in the monomer component is less than 3 weight percent.

[0122] In some preferred embodiments of the technology disclosed herein, a homopolymer containing an aromatic ring (hereinafter referred to as “monomer L”) having a Tg of 10°C or less (preferably 5°C or less or 0°C or less, more preferably -10°C or less, even more preferably -20°C or less, e.g. -25°C or less) is employed as at least part of the monomer (m1). When the content of the aromatic ring containing monomer (m1) in the monomer component (in particular, the aromatic ring containing monomer (m1) corresponding to one or both of the above-described aromatic ring multiple containing monomer and high refractive index monomer) is increased, the storage modulus G' of the adhesive tends to generally increase; however, by employing monomer L as part or all of the said monomer (m1), the increase in the storage modulus G' can be suppressed. By doing so, the refractive index can be improved while maintaining better flexibility suitable for the adhesive. The lower limit of the Tg of monomer L is not particularly limited. Considering the balance with the refractive index enhancement effect, in several embodiments, the Tg of monomer L may be, for example, -70°C or higher, -55°C or higher, or -45°C or higher. Monomer L may be used as a single type or in combination of two or more types.

[0123] As monomer L, compounds having a corresponding Tg from among the compounds included in the concept of the aromatic ring-containing monomer (m1) disclosed herein (e.g., compounds and groups of compounds exemplified above) may be appropriately adopted. One suitable example of an aromatic ring-containing monomer that can be used as monomer L is m-phenoxybenzyl acrylate (Tg of homopolymer: -35°C). Another suitable example is phenoxydiethylene glycol acrylate (Tg of homopolymer: -35°C).

[0124] The content of monomer L in monomer (m1) is not particularly limited and, for example, may be 5% by weight or more, 25% by weight or more, or 40% by weight or more. In some embodiments, from the viewpoint of making it easier to obtain an adhesive that achieves a higher level of compatibility between high refractive index and flexibility, the content of monomer L in monomer (m1) may, for example, be 50% by weight or more, 60% by weight or more, 70% by weight or more, 75% by weight or more, 85% by weight or more, 90% by weight or more, or 95% by weight or more. Substantially 100% by weight of monomer (A1) may be monomer L. In addition, in several embodiments, for example, with regard to achieving a good balance of flexibility and high refractive index suitable for an adhesive, the content of monomer L in monomer (m1) may be less than 100 wt%, 98 wt% or less, 90 wt% or less, 80 wt% or less, 70 wt% or less, 50 wt% or less, 25 wt% or less, or 10 wt% or less. The technology disclosed herein may also be implemented in an embodiment where the content of monomer L in monomer (m1) is less than 5 wt%. Monomer L may not be used.

[0125] The content of monomer L in the monomer component constituting the acrylic polymer may, for example, be 3 weight% or more, 10 weight% or more, or 25 weight% or more. In several embodiments, from the perspective of making it easier to obtain an adhesive that achieves a higher level of compatibility between high refractive index and flexibility, the content of monomer L in the monomer component may, for example, exceed 35 weight%, preferably exceed 50 weight%, exceed 70 weight%, 75 weight% or more, 85 weight% or more, 90 weight% or more, or 95 weight% or more. The content of monomer L in the above monomer component may be 100% by weight, but considering the balance between high refractive index and adhesive properties and / or optical properties, it is advantageous to keep it less than 100% by weight, preferably approximately 99% by weight or less, more preferably 98% by weight or less, and may be 96% by weight or less, 95% by weight or less, 93% by weight or less, 90% by weight or less, 85% by weight or less, 80% by weight or less, or 75% by weight or less. In some embodiments, the content of monomer L in the above monomer component may be 70% by weight or less, 50% by weight or less, 25% by weight or less, 15% by weight or less, or 5% by weight or less. The technology disclosed herein may also be carried out in an embodiment in which the content of monomer L in the monomer component is less than 3 weight%.

[0126] In some embodiments, the glass transition temperature Tg based on the composition of the monomer (m1) m1 In terms of the flexibility of the adhesive, it is advantageous for the temperature to be approximately 20°C or lower, preferably 10°C or lower (e.g., 5°C or lower), more preferably 0°C or lower, even more preferably -10°C or lower, may be -20°C or lower, or -25°C or lower. Glass transition temperature Tg m1The lower limit of is not specifically restricted. Considering the balance with the refractive index enhancement effect, in several embodiments, the glass transition temperature Tg m1 The temperature may, for example, be -70°C or higher, -55°C or higher, or -45°C or higher. The technology disclosed herein relates to a glass transition temperature Tg m1 For example, this can also be suitably implemented in an embodiment of -40℃ or higher, -35℃ or higher, -33℃ or higher, -30℃ or higher, or -25℃ or higher.

[0127] Here, the glass transition temperature Tg based on the composition of the monomer (m1) m1 This refers to the Tg obtained by Fox's formula described below, based on the composition of only the monomer (m1) among the monomer components constituting the acrylic polymer. Glass transition temperature Tg m1 It can be calculated by applying Fox's formula described below to only the monomer (m1) among the monomer components constituting the acrylic polymer, based on the glass transition temperature of the homopolymer of each aromatic ring-containing monomer used as monomer (m1) and the weight fraction of each aromatic ring-containing monomer in the total amount of monomer (m1). In an embodiment where only one type of monomer is used as monomer (m1), the Tg of the homopolymer of the corresponding monomer and the glass transition temperature Tg m1 It matches.

[0128] In several embodiments, as the aromatic ring-containing monomer (m1), monomer L (i.e., an aromatic ring-containing monomer in which the Tg of the homopolymer is 10°C or lower, preferably 5°C or lower or 0°C or lower, more preferably -10°C or lower, even more preferably -20°C or lower, for example -25°C or lower) and monomer H, which has a Tg higher than 10°C, may be used in combination. The Tg of monomer H may, for example, be greater than 10°C, greater than 15°C, or greater than 20°C. By using monomer L and monomer H in combination, for example, in a composition in which the content of the aromatic ring-containing monomer (m1) in the monomer component is relatively high, the high refractive index and flexibility of the adhesive can be achieved at a higher level. The ratio of the usage of monomer L and monomer H can be set so that this effect is suitably expressed and is not particularly limited. For example, the glass transition temperature Tg of any of the above m1 It is desirable to set the usage ratio of monomer L and monomer H to satisfy [the condition].

[0129] In some embodiments, the aromatic ring-containing monomer (m1) may preferably be selected from compounds that do not contain a structure in which two or more non-condensing aromatic rings are directly chemically bonded (e.g., a biphenyl structure). For example, an acrylic polymer composed of monomer components having a composition in which the content of a compound containing a structure in which two or more non-condensing aromatic rings are directly chemically bonded is less than 5% by weight (more preferably less than 3% by weight, and may be 0% by weight) is preferred. Limiting the amount of the compound containing a structure in which two or more non-condensing aromatic rings are directly chemically bonded in this way can be advantageous from the perspective of realizing an adhesive that balances flexibility, tackiness, and high refractive index.

[0130] (Monomer(m2))

[0131] In some embodiments of the technology disclosed herein, the monomer component constituting the acrylic polymer may further contain monomer (m2) in addition to monomer (m1). Monomer (m2) is a monomer corresponding to at least one of a monomer having a hydroxyl group (hydroxyl group-containing monomer) and a monomer having a carboxyl group (carboxyl group-containing monomer). The hydroxyl group-containing monomer is a compound having at least one hydroxyl group and at least one ethylenically unsaturated group within one molecule. The carboxyl group-containing monomer is a compound containing at least one carboxyl group and at least one ethylenically unsaturated group within one molecule. Monomer (m2) may be helpful in introducing crosslinking points into the acrylic polymer or imparting suitable cohesiveness to the adhesive. Monomer (m2) may be used alone or in combination of two or more types. Monomer (m2) is typically a monomer that does not contain an aromatic ring.

[0132] Examples of ethylenically unsaturated groups in the monomer (m2) include (meth)acryloyl groups, vinyl groups, and (meth)allyl groups. (Meth)acryloyl groups are preferred in terms of polymerization reactivity, and acryloyl groups are more preferred in terms of flexibility and adhesiveness. In terms of suppressing the reduction of flexibility of the adhesive, a compound having one ethylenically unsaturated group (i.e., a monofunctional monomer) is preferably used as the monomer (m2).

[0133] Examples of hydroxyl group-containing monomers include (meth)acrylic acid 2-hydroxyethyl, (meth)acrylic acid 2-hydroxypropyl, (meth)acrylic acid 4-hydroxybutyl, (meth)acrylic acid 6-hydroxyhexyl, (meth)acrylic acid 8-hydroxyoctyl, (meth)acrylic acid 10-hydroxydecyl, (meth)acrylic acid 12-hydroxylauryl, (meth)acrylic acid 4-hydroxymethylcyclohexyl)methyl(meth)acrylate, etc., but are not limited thereto. Examples of hydroxyl group-containing monomers that can be preferably used include acrylic acid 4-hydroxybutyl (Tg: -40°C) and acrylic acid 2-hydroxyethyl (Tg: -15°C). In terms of improving flexibility in the room temperature range, 4-hydroxybutyl acrylate with a lower Tg is more preferred. In a preferred embodiment, 50% or more by weight of the monomer (m2) (e.g., more than 50% by weight, more than 70% by weight, or more than 85% by weight) may be 4-hydroxybutyl acrylate. The hydroxyl group-containing monomer may be used alone or in combination of two or more types.

[0134] In several embodiments in which a hydroxyl group-containing monomer is used as the monomer (m2), the hydroxyl group-containing monomer may be one or more selected from compounds that do not have a methacryloyl group. Suitable examples of hydroxyl group-containing monomers that do not have a methacryloyl group include the various hydroxyalkyl acrylates described above. For example, it is preferable that more than 50% by weight, more than 70% by weight, or more than 85% by weight of the hydroxyl group-containing monomer used as the monomer (m2) is hydroxyalkyl acrylate. By using hydroxyalkyl acrylate, hydroxyl groups that help provide crosslinking points or impart appropriate cohesiveness can be introduced into the acrylic polymer, and it is also easier to obtain an adhesive with good flexibility and tackiness in the room temperature range compared to when only the corresponding hydroxyalkyl methacrylate is used.

[0135] Examples of carboxyl group-containing monomers include, in addition to acrylic monomers such as (meth)acrylic acid, (meth)acrylic acid carboxyethyl, and (meth)acrylic acid carboxypentyl, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid, but are not limited thereto. Examples of carboxyl group-containing monomers that can be preferably used include acrylic acid and methacrylic acid. Carboxyl group-containing monomers may be used alone or in combination of two or more types. Hydroxyl group-containing monomers and carboxyl group-containing monomers may be used in combination.

[0136] The content of monomer (m2) in the monomer component constituting the acrylic polymer is not particularly limited and can be set according to the purpose. In some embodiments, the content of the monomer (m2) may be, for example, 0.01 weight% or more, 0.1 weight% or more, or 0.5 weight% or more. In some embodiments, for the purpose of obtaining a higher usage effect, it is preferable that the content of the monomer (A2) be 1 weight% or more, 2 weight% or more, or 4 weight% or more. The upper limit of the content of the monomer (m2) in the monomer component is set so that the sum with the content of other monomers does not exceed 100 weight%. In several embodiments, the content of the monomer (m2) is suitable to be, for example, 30% by weight or less or 25% by weight or less, and from the perspective of making the content of the monomer (m1) relatively high to facilitate high refractive index, it is preferable to have it at 20% by weight or less, more preferable to have it at 15% by weight or less, and it may be less than 12% by weight, less than 10% by weight, or less than 7% by weight.

[0137] In an embodiment in which a hydroxyl group-containing monomer is used as the monomer (m2), the content of the hydroxyl group-containing monomer in the monomer component is not particularly limited and may be, for example, 0.01 weight% or more (preferably 0.1 weight% or more, more preferably 0.5 weight% or more). In several embodiments, the content of the hydroxyl group-containing monomer is preferably 1 weight% or more of the monomer component, may be 2 weight% or more, or 4 weight% or more. The upper limit of the content of the hydroxyl group-containing monomer in the monomer component is set so that the total content with other monomers does not exceed 100% by weight, and it is suitable to be, for example, 30% by weight or less or 25% by weight or less, and from the perspective of making the content of monomer (m1) relatively high to facilitate high refractive index, it is preferable to be 20% by weight or less, more preferable to be 15% by weight or less, and it may be less than 12% by weight, less than 10% by weight, or less than 7% by weight.

[0138] In an embodiment in which a carboxyl group-containing monomer is used as the monomer (m2), the content of the carboxyl group-containing monomer in the monomer component is not particularly limited and may be, for example, 0.01 weight% or more (preferably 0.1 weight% or more, more preferably 0.3 weight% or more). In several embodiments, the content of the carboxyl group-containing monomer may be 1 weight% or more, 2 weight% or more, or 4 weight% or more. The upper limit of the content of the carboxyl group-containing monomer in the monomer component is set so that the total amount with other monomers does not exceed 100% by weight, and it is suitable to be, for example, 30% by weight or less or 25% by weight or less. From the perspective of making it easier to achieve a high refractive index by increasing the content of monomer (m1) relatively, it is preferable to have it at 20% by weight or less, more preferable to have it at 15% by weight or less, and it may be less than 12% by weight or less than 10% by weight. In several embodiments, from the perspective of improving the flexibility of the adhesive, the content of the carboxyl group-containing monomer is advantageous to have it at less than 7% by weight, preferably less than 5% by weight, and may be less than 3% by weight, less than 1% by weight, or less than 0.5% by weight. The technology disclosed herein can be preferably implemented, for example, in an embodiment in which only a hydroxyl group-containing monomer is used as the monomer (m2), that is, in an embodiment in which a carboxyl group-containing monomer is not used.

[0139] The total content of monomer (m1) and monomer (m2) in the monomer components constituting the acrylic polymer may, for example, be 31% by weight or more, preferably 51% by weight or more, 61% by weight or more, or 71% by weight or more. In some embodiments, the total content of monomer (m1) and monomer (m2) in the monomer components constituting the acrylic polymer may, for example, be 76% by weight or more, preferably 81% by weight or more, 86% by weight or more, 91% by weight or more, 96% by weight or more, 99% by weight or more, and substantially 100% by weight, from the viewpoint of facilitating the suitable exertion of the effects of these monomers.

[0140] (Monomer m3)

[0141] The monomer components constituting the acrylic polymer may include monomers other than the monomer (m1) and the monomer (m2) as needed. An example of such optional components is an alkyl (meth)acrylate (hereinafter also referred to as "monomer (m3)"). Monomer (m3) can help adjust the flexibility of the adhesive or improve compatibility within the adhesive.

[0142] As a monomer (m3), having 1 to 20 carbon atoms (i.e., C 1-20 d) An alkyl (meth)acrylate having a straight-chain or branched-chain alkyl group at the ester end may be preferably used. C1 -20Specific examples of alkyl (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, and dodecyl (meth)acrylate. Examples include (meth)acrylate tridecyl, (meth)acrylate tetradecyl, (meth)acrylate pentadecyl, (meth)acrylate hexadecyl, (meth)acrylate heptadecyl, (meth)acrylate stearyl, (meth)acrylate isostearyl, (meth)acrylate nonadecyl, (meth)acrylate eicosyl, etc., but are not limited to these.

[0143] In some embodiments, an alkyl (meth)acrylate having a Tg of -20°C or lower (more preferably -40°C or lower, e.g. -50°C or lower) of the homopolymer may be preferably employed as at least part of the monomer (m3). Such a low-Tg alkyl (meth)acrylate can help improve the flexibility of the adhesive. The lower limit of the Tg of the alkyl (meth)acrylate is not particularly limited and may be, for example, -85°C or higher, -75°C or higher, -65°C or higher, or -60°C or higher. Specific examples of the low-Tg alkyl (meth)acrylate include n-butyl acrylate (BA), 2-ethylhexyl acrylate (2EHA), isononyl acrylate (iNA), etc.

[0144] In several embodiments of using monomer (m3), it is preferable that at least a portion of the monomer (m3) is an alkyl acrylate in terms of flexibility or adhesiveness. For example, it is preferable that 50% or more by weight (more preferably 75% or more by weight, even more preferably 90% or more by weight) of the monomer (m3) is an alkyl acrylate. An embodiment may be used in which only one or two or more alkyl acrylates are used as monomer (m3) and alkyl methacrylates are not used.

[0145] In an embodiment in which the monomer component comprises an alkyl (meth)acrylate, the content of the alkyl (meth)acrylate in the monomer component can be set so that the effect of use is appropriately exhibited. In some embodiments, the content of the alkyl (meth)acrylate may be, for example, 1 weight% or more, 3 weight% or more, 5 weight% or more, or 8 weight% or more. In some embodiments, the content of the alkyl (meth)acrylate may be 15 weight% or more, 30 weight% or more, or 45 weight% or more. The upper limit of the content of the monomer (m3) in the monomer component is set so that the sum with the content of other monomers does not exceed 100 weight%, and may be, for example, less than 50 weight%. In some embodiments, the content of the monomer (m3) may be, for example, less than 35 weight%. Generally, since the refractive index of alkyl (meth)acrylates is relatively low, in order to achieve a high refractive index, it is advantageous to limit the content of monomer (m3) in the monomer component and to make the content of monomer (m1) relatively high. In this regard, it is advantageous for the content of monomer (m3) to be 24% by weight or less of the monomer component, preferably less than 23% by weight, more preferably less than 20% by weight, and may be less than 17% by weight, less than 12% by weight, less than 7% by weight, less than 3% by weight, or less than 1% by weight. Monomer (m3) may not be substantially used.

[0146] (Other monomers)

[0147] The monomer components constituting the acrylic polymer may, if necessary, include monomers other than the above monomers (m1), (m2), and (m3) (hereinafter referred to as "other monomers"). The above other monomers may be used for purposes such as adjusting the Tg of the acrylic polymer, adjusting adhesive performance, and improving compatibility within the adhesive layer. The above other monomers may be used as a single type or in combination of two or more types.

[0148] Examples of the above other monomers include monomers having functional groups other than hydroxyl and carboxyl groups (functional group-containing monomers). For example, other monomers that can improve the cohesiveness or heat resistance of adhesives include sulfonic acid group-containing monomers, phosphate group-containing monomers, cyano group-containing monomers, etc. In addition, monomers that can introduce functional groups capable of serving as crosslinking points into acrylic polymers, or contribute to improving peel strength or compatibility within the adhesive layer, may include amide group-containing monomers (e.g., (meth)acrylamide, N-methylol(meth)acrylamide, etc.), amino group-containing monomers (e.g., aminoethyl(meth)acrylate, N,N-dimethylaminoethyl(meth)acrylate, etc.), monomers having a nitrogen atom-containing ring (e.g., N-vinyl-2-pyrrolidone, N-(meth)acryloylmorpholine, etc.), imide group-containing monomers, epoxy group-containing monomers, keto group-containing monomers, isocyanate group-containing monomers, alkoxysilyl group-containing monomers, etc. Furthermore, among monomers having a nitrogen atom-containing ring, there are some that correspond to amide group-containing monomers, such as N-vinyl-2-pyrrolidone. The same applies to the relationship between the monomer having the above-mentioned nitrogen atom-containing ring and the amino group-containing monomer.

[0149] Other monomers that can be used in addition to the above functional group-containing monomers include vinyl ester monomers such as vinyl acetate; non-aromatic ring-containing (meth)acrylates such as cyclohexyl (meth)acrylate and isobornyl (meth)acrylate; olefin monomers such as ethylene, butadiene, and isobutylene; chlorine-containing monomers such as vinyl chloride; alkoxy group-containing monomers such as methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, and ethoxyethoxyethyl (meth)acrylate; vinyl ether monomers such as methyl vinyl ether; etc. As a suitable example of other monomers that can be used for purposes such as improving the flexibility of adhesives, ethoxyethoxyethyl acrylate (alias: ethyl carbitol acrylate, Tg of homopolymer: -67°C) may be cited.

[0150] When using the above-mentioned other monomer, the amount used is not particularly limited and can be appropriately set within a range where the total amount of the monomer component does not exceed 100% by weight. In several embodiments, from the perspective of making it easier to exhibit the refractive index improvement effect by using monomer (m1), the content of the above-mentioned other monomer in the monomer component may be, for example, approximately 35% by weight or less, approximately 25% by weight or less (e.g., 0 to 25% by weight), approximately 20% by weight or less (e.g., 0 to 20% by weight), approximately 10% by weight or less, approximately 5% by weight or less, or, for example, approximately 1% by weight or less. The technology disclosed herein may preferably be implemented in an embodiment where the monomer component substantially does not contain the above-mentioned other monomer.

[0151] In some embodiments, the monomer component constituting the acrylic polymer may be a composition in which the amount of methacryloyl group-containing monomer used is suppressed to a predetermined amount or less. The amount of methacryloyl group-containing monomer in the monomer component may, for example, be less than 5 weight%, less than 3 weight%, less than 1 weight%, or less than 0.5 weight%. Limiting the amount of methacryloyl group-containing monomer in this way may be advantageous from the perspective of realizing an adhesive that balances flexibility, tackiness, and high refractive index well. The monomer component constituting the acrylic polymer may be a composition that does not contain methacryloyl group-containing monomer (for example, a composition consisting only of acryloyl group-containing monomer).

[0152] In several embodiments, regarding the base polymer (e.g., acrylic polymer) of the adhesive layer, the monomer component is preferably limited in the amount of carboxyl group-containing monomer used to suppress discoloration or discoloration (e.g., yellowing) of the adhesive. The amount of carboxyl group-containing monomer used in the monomer component may be, for example, less than 1 weight%, preferably less than 0.5 weight%, more preferably less than 0.3 weight%, less than 0.1 weight%, or less than 0.05 weight%. Limiting the amount of carboxyl group-containing monomer in this way is also advantageous from the perspective of suppressing corrosion of metal materials (e.g., metal wiring or metal films that may exist on a substrate) that may be placed in contact with or close to the adhesive disclosed herein. The technology disclosed herein may preferably be implemented in an embodiment in which the monomer component does not contain a carboxyl group-containing monomer.

[0153] For the same reason, in several embodiments, it is preferable that the monomer component constituting the base polymer of the adhesive layer has a limited amount of monomer having an acidic functional group (including sulfonic acid groups, phosphate groups, etc., in addition to carboxyl groups). As for the amount of monomer containing acidic functional groups in the monomer component of such embodiments, the preferred amount of the carboxyl group-containing monomer described above may be applied. The technology disclosed herein may be preferably implemented in an embodiment in which the monomer component does not contain an acidic group-containing monomer (i.e., an embodiment in which the base polymer of the adhesive layer is acid-free).

[0154] (Glass transition temperature Tg of base polymer T )

[0155] In some embodiments, the base polymer of the adhesive layer (e.g., an acrylic polymer) has a glass transition temperature Tg based on the composition of the monomer components constituting the polymer. T a. It is suitable for the temperature to be approximately 20°C or lower, preferably approximately 10°C or lower, more preferably 0°C or lower, and may be -10°C or lower, -20°C or lower, -25°C or lower, -28°C or lower, or -30°C or lower. Glass transition temperature Tg T A low value can be advantageous in terms of improving the flexibility of the adhesive. In addition, the glass transition temperature Tg T For example, it may be -60°C or higher, and from the perspective of facilitating the high refractive index of the adhesive, it is preferably -50°C or higher, more preferably -45°C or higher, it may be -40°C or higher, -35°C or higher, -25°C or higher, -15°C or higher, and -5°C or higher.

[0156] Here, the glass transition temperature Tg of the polymer TUnless otherwise specified, it refers to the glass transition temperature obtained by Fox's formula based on the composition of the monomer components constituting the polymer. Fox's formula is a relationship between the Tg of a copolymer and the glass transition temperature Tgi of a homopolymer formed by homopolymerizing each of the monomers constituting the copolymer, as described below.

[0157] 1 / Tg=Σ(Wi / Tgi)

[0158] In the above Fox formula, Tg represents the glass transition temperature of the copolymer (unit: K), Wi represents the weight fraction of monomer i in the copolymer (copolymer ratio on a weight basis), and Tgi represents the glass transition temperature of the homopolymer of monomer i (unit: K).

[0159] For the glass transition temperature of the homopolymer used to calculate Tg, the value listed in known sources such as the “Polymer Handbook” (3rd edition, John Wiley & Sons, Inc., 1989) shall be used. For monomers for which multiple types of values ​​are listed in the Polymer Handbook, the highest value shall be adopted. If the Tg of the homopolymer is not listed in known sources, the value obtained by the measurement method described in Japanese Patent Application Publication No. 2007-51271 shall be used.

[0160] (Method for preparing base polymer)

[0161] In the technology disclosed herein, the method for obtaining the base polymer of the adhesive layer (e.g., an acrylic polymer (A) composed of monomer components as described above) is not particularly limited, and known polymerization methods such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, and photopolymerization may be appropriately employed. In several embodiments, solution polymerization may be preferably employed. The polymerization temperature when performing solution polymerization can be appropriately selected depending on the type of monomer and solvent used, the type of polymerization initiator, etc., and can be, for example, 20°C to 170°C (typically 40°C to 140°C).

[0162] The solvent used for solution polymerization (polymerization solvent) can be appropriately selected from conventionally known organic solvents. For example, any one solvent or a mixture of two or more solvents selected from aromatic compounds such as toluene (typically aromatic hydrocarbons); acetic acid esters such as ethyl acetate; aliphatic or alicyclic hydrocarbons such as hexane or cyclohexane; halogenated alkanes such as 1,2-dichloroethane; lower alcohols such as isopropyl alcohol (e.g., monohydric alcohols having 1 to 4 carbon atoms); ethers such as tert-butylmethyl ether; ketones such as methyl ethyl ketone; etc. may be used.

[0163] The initiator used for polymerization can be appropriately selected from conventionally known polymerization initiators depending on the type of polymerization method. For example, one or more types of azo-based polymerization initiators, such as 2,2'-azobisisobutyronitrile (AIBN), may be preferably used. Other examples of polymerization initiators include persulfates such as potassium persulfate; peroxide-based initiators such as benzoyl peroxide and hydrogen peroxide; substituted ethane-based initiators such as phenyl-substituted ethane; aromatic carbonyl compounds; etc. As yet another example of a polymerization initiator, redox-based initiators formed by a combination of a peroxide and a reducing agent may be cited. The polymerization initiator may be used as a single type or in combination of two or more types. The amount of polymerization initiator used can be a normal amount and, for example, can be selected from a range of about 0.005 to 1 part by weight (typically about 0.01 to 1 part by weight) per 100 parts by weight of monomer components.

[0164] In the above polymerization, various conventionally known chain transfer agents may be used as needed. For example, mercaptans such as n-dodecyl mercaptan, t-dodecyl mercaptan, thioglycolic acid, and α-thioglycerol may be used. Alternatively, a chain transfer agent that does not contain a sulfur atom (non-sulfur chain transfer agent) may be used. Examples of non-sulfur chain transfer agents include anilines such as N,N-dimethylaniline and N,N-diethylaniline; terpenoids such as α-pinene and terpinolene; and styrenes such as α-methylstyrene and α-methylstyrene dimer. A single type of chain transfer agent may be used alone or in combination of two or more types. When using a chain transfer agent, the amount used may be, for example, approximately 0.01 to 1 weight part per 100 weight parts of the monomer raw material.

[0165] The weight-average molecular weight (Mw) of the base polymer is not particularly limited, and is, for example, approximately 10×10 4 Up to 500×10 4It can be in the range of. In terms of adhesive performance, the Mw of the base polymer is approximately 20×10 4 Up to 400×10 4 (More preferably, approximately 30×10 4 Up to 150×10 4 , for example, approximately 50×10 4 Up to 130×10 4 It is desirable to be within the range of ).

[0166] Here, the Mw of the polymer can be obtained by converting it to polystyrene using gel permeation chromatography (GPC). Specifically, it can be obtained by measuring under the following conditions using the product name “HLC-8220GPC” (manufactured by Tosho Co., Ltd.) as a GPC measuring device.

[0167] [GPC Measurement Conditions]

[0168] Sample concentration: 0.2 wt% (tetrahydrofuran solution)

[0169] Sample injection volume: 10μL

[0170] Eluent: Tetrahydrofuran (THF)

[0171] Flow rate (velocity): 0.6 mL / min

[0172] Column temperature (measurement temperature): 40℃

[0173] Column:

[0174] Sample Column: 1 unit of Product Name "TSKguardcolumn SuperHZ-H" + 2 units of Product Name "TSKgel SuperHZM-H" (Made by Dososa)

[0175] Reference Column: Product Name "TSKgel SuperH-RC" 1 unit (Doso Co.)

[0176] Detector: Parallax Refractometer (RI)

[0177] Standard sample: Polystyrene

[0178] (Refractive index enhancer)

[0179] In some embodiments of the technology disclosed herein, the adhesive layer described above (e.g., an acrylic adhesive layer) may contain, if necessary, a refractive index enhancer in addition to the base polymer. Here, the term "refractive index enhancer" in this specification refers to a material that can increase the refractive index of the adhesive layer through its use. As the refractive index enhancer, a material having a higher refractive index than the refractive index of the adhesive layer containing the refractive index enhancer may be preferably used. Furthermore, as the refractive index enhancer, a material having a higher refractive index than the base polymer of the adhesive layer containing the refractive index enhancer (e.g., an acrylic polymer (A)) may be preferably used. By appropriately using the refractive index enhancer, a higher refractive index and practical adhesive performance can be suitably combined. In some embodiments, the refractive index enhancer is preferably an organic material. The organic material used as the refractive index enhancer may be a polymer or a nonpolymer. Additionally, it may or may not have polymerizable functional groups. Refractive index improvers may be used as a single type or in combination of two or more types.

[0180] Refractive index improver (e.g., additive described below (H ROThe refractive index of the refractive index improver can be set within an appropriate range based on its relative relationship with the refractive index of the base polymer, and is therefore not limited to a specific range. The refractive index of the refractive index improver can be, for example, greater than 1.55, greater than 1.56, or greater than 1.57, and can also be selected from a range higher than the refractive index of the base polymer. From the perspective of increasing the refractive index of the adhesive, in several embodiments, it is advantageous for the refractive index improver to be 1.58 or higher, preferable to be 1.60 or higher, more preferable to be 1.63 or higher, and it may be 1.65 or higher, 1.70 or higher, or 1.75 or higher. With a refractive index improver having a higher refractive index, the desired refractive index can be achieved even with the use of a smaller amount of the improver. This is desirable from the perspective of suppressing the degradation of adhesive properties or optical properties. Although the upper limit of the refractive index of the refractive index improver is not specifically limited, from the perspective of compatibility within the adhesive and ease of achieving both high refractive index and flexibility suitable for the adhesive, for example, it may be 3,000 or less, 2,500 or less, 2,000 or less, 1,950 or less, 1,900 or less, or 1,850 or less.

[0181] In several aspects, a refractive index improver (e.g., the additive described below (H RO Refractive index n of )) b and the refractive index n of the base polymer a The difference of, that is, n b -n a (Hereafter, 「Δn A (also called 」) is set to become greater than 0. In several modalities, Δn A is, for example, 0.02 or greater, and may be 0.05 or greater, 0.07 or greater, 0.10 or greater, 0.15 or greater, 0.20 or greater, or 0.25 or greater. Δn ABy selecting a base polymer and a refractive index improver such that is greater than , the refractive index enhancement effect due to the use of the refractive index improver tends to increase. Furthermore, in terms of compatibility within the adhesive layer or the transparency of the adhesive layer, in several embodiments, Δn A For example, it may be 0.70 or less, 0.60 or less, 0.50 or less, 0.40 or less, or 0.35 or less.

[0182] In several aspects, a refractive index improver (e.g., the additive described below (H RO Refractive index n of )) b Wow, the refractive index n of the adhesive layer containing the refractive index improver. T The difference of, that is, n b -n T (Hereafter, 「Δn B (also called 」) is set to become greater than 0. In several modalities, Δn B is, for example, 0.02 or greater, and may be 0.05 or greater, 0.07 or greater, 0.10 or greater, 0.15 or greater, 0.20 or greater, or 0.25 or greater. Δn B By selecting the composition of the adhesive layer and the refractive index improver so that is greater than , the refractive index improvement effect due to the use of the refractive index improver tends to increase. In addition, in terms of compatibility within the adhesive layer or the transparency of the adhesive layer, in several embodiments, Δn B For example, it may be 0.70 or less, 0.60 or less, 0.50 or less, 0.40 or less, or 0.35 or less.

[0183] The amount of refractive index improver used per 100 parts by weight of base polymer (or the total amount thereof in cases where multiple types of refractive index improvers are used) is not particularly limited and can be set according to the purpose. From the perspective of increasing the refractive index of the adhesive, the amount of refractive index improver used per 100 parts by weight of base polymer can be, for example, 1 part by weight or more, it is advantageous to use 3 parts by weight or more, it is preferable to use 5 parts by weight or more, it may be 7 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, or 20 parts by weight or more. In addition, in several embodiments, the amount of refractive index improver used per 100 parts by weight of base polymer can be, for example, 80 parts by weight or less, and from the perspective of achieving a good balance between increasing the refractive index of the adhesive and suppressing the degradation of adhesive properties or optical properties, it is advantageous to use 60 parts by weight or less, and it is preferable to use 45 parts by weight or less. In several embodiments in which adhesive or optical properties are given greater importance, the amount of refractive index improver used per 100 parts by weight of base polymer may, for example, be 30 parts by weight or less, 20 parts by weight or less, 15 parts by weight or less, 10 parts by weight or less, 5 parts by weight or less, or 3 parts by weight or less. The technology disclosed herein may preferably be implemented in an embodiment in which the amount of refractive index improver used per 100 parts by weight of base polymer in the adhesive layer is less than 1 part by weight, or in which the refractive index improver is not substantially used. Here, "substantially not used" means not using it at least intentionally.

[0184] (Additive (H RO ))

[0185] In several embodiments, as a refractive index enhancer, an organic material having a higher refractive index than the base polymer may be preferably employed. Hereinafter, such an organic material is referred to as an "additive (H RO There are cases where it is indicated as )」. Here, the above "HRO " indicates that it is an organic material with a high refractive index. A base polymer (e.g., an acrylic polymer, preferably an acrylic polymer (A)) and an additive (H RO By using a combination of ), it is possible to realize an adhesive that more suitably balances refractive index and adhesive properties (peele strength, flexibility, etc.) and / or optical properties (total light transmittance, haze value, etc.). Additive (H RO The organic material used as an additive (H) may be a polymer or a non-polymer. In addition, it may or may not have polymerizable functional groups. RO ) can be used as a single type or in combination of two or more types.

[0186] Additive (H RO The refractive index of ) is measured using an Abbe refractive index meter, just like the refractive index of the monomer, under conditions of a measurement wavelength of 589 nm and a measurement temperature of 25°C. If a nominal value of the refractive index at 25°C is provided by the manufacturer, etc., that nominal value may be adopted.

[0187] Additive (H RO The molecular weight of the organic material used as ) is not particularly limited and can be selected according to the purpose. In terms of achieving a good balance between the effect of increasing the refractive index and other properties (e.g., optical properties such as flexibility suitable for adhesives and haze), in several embodiments, the additive (H RO The molecular weight of ) is suitably less than approximately 10,000, preferably less than 5,000, more preferably less than 3,000 (e.g., less than 1,000), and may be less than 800, less than 600, less than 500, or less than 400. Additive (H RO The fact that the molecular weight of ) is not too large can be advantageous in terms of improving compatibility within the adhesive layer. In addition, the additive (HRO The molecular weight of ) may, for example, be 130 or more, or 150 or more. In several embodiments, the additive (H RO The molecular weight of ) is the corresponding additive (H RO From the perspective of increasing the refractive index of ), it is preferable that it be 170 or higher, more preferable that it be 200 or higher, and it may be 230 or higher, 250 or higher, 270 or higher, 500 or higher, 1000 or higher, or 2000 or higher. In several embodiments, a polymer having a molecular weight of about 1000 to 10000 (e.g., 1000 or more and less than 5000) is used as an additive (H RO It can be used as ).

[0188] Additive (H RO As for the molecular weight of ), for a nonpolymer or a polymer with a low degree of polymerization (e.g., about 2 to 5mers), the molecular weight calculated based on the chemical structure or the value measured using matrix-assisted laser deionization time-of-flight mass spectrometry (MALDI-TOF-MS) may be used. Additive (H RO In the case where the polymer has a higher degree of polymerization, the weight average molecular weight (Mw) based on GPC performed under appropriate conditions may be used. If a nominal value of the molecular weight is provided by the manufacturer, etc., that nominal value may be adopted.

[0189] Additive (H RO Examples of organic materials that can be options include, but are not limited to, organic compounds having aromatic rings, organic compounds having heterocyclic rings (which may be aromatic rings or non-aromatic heterocyclic rings).

[0190] Additive (H RO The aromatic ring of the organic compound having the above aromatic ring (hereinafter also referred to as the “aromatic ring-containing compound”) used as a monomer (m1) can be selected from the same as the aromatic ring of the compound used as a monomer (m1).

[0191] The above-mentioned aromatic ring may have one or more substituents on the ring constituent atoms, or it may not have any substituents. When having substituents, examples of such substituents include, but are not limited to, alkyl groups, alkoxy groups, aryloxy groups, hydroxyl groups, hydroxyloxy groups, glycidyloxy groups, etc. In the case of substituents containing carbon atoms, the number of carbon atoms included in the substituent may be, for example, 1 to 10, advantageously 1 to 6, preferably 1 to 4, more preferably 1 to 3, and for example, 1 or 2. In some embodiments, the above-mentioned aromatic ring may not have substituents on the ring constituent atoms, or may be an aromatic ring having one or more substituents selected from the group consisting of alkyl groups, alkoxy groups, and halogen atoms (e.g., bromine atoms).

[0192] Additive (H RO Examples of aromatic ring-containing compounds that can be used as ) include, for example: a compound that can be used as a monomer (m1); an oligomer comprising the compound that can be used as a monomer (m1) as a monomer unit; a compound having a structure in which, excluding the portion constituting the ethylenically unsaturated group of the compound that can be used as a monomer (m1), a hydrogen atom or a group that does not have an ethylenically unsaturated group (e.g., a hydroxyl group, an amino group, a halogen atom, an alkyl group, an alkoxy group, a hydroxyalkyl group, a hydroxyalkyloxy group, a glycidyloxy group, etc.) is substituted from the compound that can be used as a monomer (m1); but are not limited thereto. Additive (H RONon-limiting embodiments of aromatic ring-containing compounds that can be used as ) include aromatic ring-containing monomers such as benzyl acrylate, m-phenoxybenzyl acrylate, 2-(o-phenylphenoxy)ethyl acrylate, phenoxyethyl acrylate, phenoxydiethylene glycol acrylate, phenoxypolyethylene glycol acrylate, 2-hydroxy-3-phenoxypropyl acrylate, the monomer having the fluorene structure described above, the monomer having the dinaphthothiophen structure, the monomer having the dibenzothiophen structure; Aromatic ring-containing compounds that do not have ethylenically unsaturated groups, such as 3-phenoxybenzyl alcohol, dinaphthothiophene and their derivatives (e.g., compounds having a structure in which one or more substituents selected from hydroxyl groups, methanol groups, diethanol groups, glycidyl groups, etc. are bonded to a dinaphthothiophene ring, etc.). Additionally, the aromatic ring-containing compound may be an oligomer comprising such an aromatic ring-containing monomer as a monomer unit (preferably an oligomer with a molecular weight of approximately 5,000 or less, more preferably approximately 1,000 or less; for example, a low polymer of about 2 to 5mers). The oligomer may be, for example: a homopolymer of the aromatic ring-containing monomer; a copolymer of one or more aromatic ring-containing monomers; a copolymer of one or more aromatic ring-containing monomers and another monomer; etc. As other monomers mentioned above, one or more monomers that do not have an aromatic ring may be used.

[0193] In several aspects, the additive (H ROAs such, an organic compound having two or more aromatic rings in one molecule (hereinafter also referred to as a "compound containing multiple aromatic rings") may be preferably employed, as it is easy to obtain a high refractive index effect. The compound containing multiple aromatic rings may or may not have polymerizable functional groups such as ethylenically unsaturated groups. Furthermore, the compound containing multiple aromatic rings may be a polymer or a nonpolymer. In addition, the polymer may be an oligomer containing a monomer containing multiple aromatic rings as a monomer unit (preferably an oligomer with a molecular weight of approximately 5,000 or less, more preferably approximately 1,000 or less; for example, a low polymer of about 2 to 5 mers). The oligomer may be, for example: a homopolymer of a monomer containing multiple aromatic rings; a copolymer of one or more monomers containing multiple aromatic rings; a copolymer of one or more monomers containing multiple aromatic rings and another monomer; etc. The other monomer mentioned above may be an aromatic ring-containing monomer that does not correspond to an aromatic ring-containing monomer, may be a monomer that does not have an aromatic ring, or may be a combination thereof.

[0194] Non-limiting examples of compounds containing multiple aromatic rings include compounds having a structure in which two or more non-condensing aromatic rings are bonded through linking groups, compounds having a structure in which two or more non-condensing aromatic rings are chemically bonded directly (i.e., without through other atoms), compounds having a condensing aromatic ring structure, compounds having a fluorene structure, compounds having a dinaphthothiophene structure, compounds having a dibenzothiophene structure, etc. Compounds containing multiple aromatic rings may be used as a single type or in combination of two or more types.

[0195] Specific examples of compounds having the above-described fluorene structure include, in addition to the monomer having the above-described fluorene structure or the oligomer which is a homopolymer or copolymer of such monomer, 9,9-bis(4-hydroxyphenyl)fluorene (refractive index: 1.68), 9,9-bis(4-aminophenyl)fluorene (refractive index: 1.73), 9,9-bis(4-hydroxy-3-methylphenyl)fluorene (refractive index: 1.68), 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene (refractive index: 1.65), 9,9-bisphenylfluorene and its derivatives.

[0196] Specific examples of compounds having the above-described dinaphthothiophen structure include, in addition to the monomer having the above-described dinaphthiophen structure or the oligomer which is a homopolymer or copolymer of such monomer, dinaphthiophen (refractive index: 1.808); hydroxyalkyldinaphthiophen such as 6-hydroxymethyldinaphthiophen (refractive index: 1.766); dihydroxydinaphthiophen such as 2,12-dihydroxydinaphthiophen (refractive index: 1.750); dihydroxyalkyloxydinaphthiophen such as 2,12-dihydroxyethyloxydinaphthiophen (refractive index: 1.677); and diglycidyloxydinaphthiophen such as 2,12-diglycidyloxydinaphthiophen (refractive index: 1.723). Examples include dinaphthiophen having two or more ethylenically unsaturated groups, such as 2,12-diallyloxydinaphthiophen (abbreviation: 2,12-DAODNT, refractive index 1.729); and other dinaphthiophens and their derivatives.

[0197] Specific examples of compounds having the above-described dibenzothiophen structure include, in addition to the monomer having the above-described dibenzothiophen structure or the oligomer which is a homopolymer or copolymer of such monomer, dibenzothiophen (refractive index: 1.607), 4-dimethyldibenzothiophen (refractive index: 1.617), 4,6-dimethyldibenzothiophen (refractive index: 1.617), etc.

[0198] Additive (H ROExamples of organic compounds having a heterocyclic ring (hereinafter also referred to as heterocyclic-containing organic compounds) that can be an option include thioepoxy compounds and compounds having a triazine ring. Examples of thioepoxy compounds include bis(2,3-epithiopropyl)disulfide and its polymer (refractive index 1.74) described in Japanese Patent Publication No. 3712653. Examples of compounds having a triazine ring include compounds having at least one triazine ring (e.g., 3 to 40, preferably 5 to 20) within one molecule. Furthermore, since triazine rings are aromatic, compounds having a triazine ring are included in the concept of aromatic-ring containing compounds, and compounds having multiple triazine rings are also included in the concept of aromatic-ring containing compounds.

[0199] In several aspects, the additive (H RO As for ), a compound not having an ethylenically unsaturated group can be preferably employed. By doing so, the deterioration of the adhesive composition due to heat or light (progression of gelation or decrease in leveling properties due to increased viscosity) can be suppressed, thereby increasing storage stability. An additive not having an ethylenically unsaturated group (H RO Adopting ) is, the corresponding additive (H RO It is also desirable from the perspective of suppressing dimensional changes or deformation (bending, rippling, etc.) and optical distortion caused by the reaction of ethylenically unsaturated groups in an adhesive sheet having an adhesive layer including ), or in a laminate including said adhesive sheet.

[0200] Additive (H ROIn the embodiment in which an oligomer is used as a ), the oligomer can be obtained by polymerizing the corresponding monomer component by a known method. When the oligomer is prepared by radical polymerization, polymerization can be carried out by appropriately adding a polymerization initiator, a chain transfer agent, an emulsifier, etc., used for radical polymerization to the monomer component. The polymerization initiator, the chain transfer agent, the emulsifier, etc., used for radical polymerization are not particularly limited and can be appropriately selected and used. Furthermore, the weight-average molecular weight of the oligomer can be controlled by the amount of polymerization initiator and chain transfer agent used and the reaction conditions, and the amount used is appropriately adjusted according to the type of these.

[0201] Examples of the above-mentioned chain transfer agents include lauryl mercaptan, glycidyl mercaptan, mercaptoacetic acid, 2-mercaptoethanol, α-thioglycerol, thioglycolic acid, 2-ethylhexyl thioglycolic acid, 2,3-dimercapto-1-propanol, etc. The chain transfer agent may be used alone or in a mixture of two or more types. The amount of chain transfer agent used can be set so that an oligomer of a desired weight-average molecular weight is obtained, depending on the composition of the monomer component used in the synthesis of the oligomer and the type of chain transfer agent. In several embodiments, the amount of chain transfer agent used per 100 parts by weight of the total amount of monomer used in the synthesis of the oligomer is appropriately about 15 parts by weight or less, may be 10 parts by weight or less, or may be about 5 parts by weight or less. The lower limit of the amount of chain transfer agent used per 100 parts by weight of the total amount of monomer used in the synthesis of the oligomer is not specifically limited, but, for example, it may be 0.01 parts by weight or more, 0.1 parts by weight or more, 0.5 parts by weight or more, or 1 part by weight or more.

[0202] As a refractive index improver, the additive (H RO In an embodiment using ), an additive (H) per 100 parts by weight of base polymer ROThe amount of ) used (or the total amount in the case of using multiple types of compounds) is not particularly limited and can be set according to the purpose. From the perspective of increasing the refractive index of the adhesive, an additive (H ) per 100 parts by weight of base polymer RO The amount of ) used can, for example, be 1 part by weight or more, it is advantageous to use 3 parts by weight or more, it is preferable to use 5 parts by weight or more, it may be 7 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, or 20 parts by weight or more. In several embodiments, the additive (H) per 100 parts by weight of base polymer RO The amount of ) used can be, for example, 80 parts by weight or less, and from the perspective of achieving a good balance between increasing the refractive index of the adhesive and suppressing the degradation of adhesive or optical properties, it is advantageous to use 60 parts by weight or less, and it is preferable to use 45 parts by weight or less. In several embodiments that place greater emphasis on adhesive or optical properties, an additive (H) per 100 parts by weight of base polymer RO The amount of ) used may be, for example, 30 parts by weight or less, 20 parts by weight or less, 15 parts by weight or less, or 10 parts by weight or less.

[0203] (Plasticizing material)

[0204] In several embodiments of the adhesive sheet disclosed herein, the adhesive layer may include a plasticizing material having a lower molecular weight than the base polymer in addition to the base polymer (e.g., acrylic polymer (A)) as described above. By using the plasticizing material, the flexibility of the adhesive layer can be increased, thereby improving adhesion to the substrate, as well as the flexibility and conformability to deformation of the adhesive sheet as a whole. As for the plasticizing material, an organic material may be preferably employed in terms of compatibility and transparency within the adhesive layer. The plasticizing material may be the refractive index improver described above (e.g., the additive (H RO It may also be a material that can be used as )).

[0205] The molecular weight of the plasticizing material may be lower than that of the base polymer and is not particularly limited. In several embodiments, the molecular weight of the plasticizing material may be 30,000 or less, 25,000 or less, less than 10,000, or preferably less than 5,000, less than 3,000 (e.g., less than 1,000), less than 800, less than 600, less than 500, or less than 400, from the perspective of facilitating the expression of a plasticizing effect. Not having a molecular weight of the plasticizing material that is too large can be advantageous from the perspective of improving compatibility within the adhesive layer. In addition, in some embodiments, the molecular weight of the plasticizing material is preferably 130 or higher, 150 or higher, 170 or higher, 200 or higher, 250 or higher, or 300 or higher from the perspective of facilitating the exertion of a sufficient plasticizing effect. In some embodiments, the molecular weight of the plasticizing material may be 500 or higher, 1000 or higher, or 2000 or higher. It is also desirable that the molecular weight of the plasticizing material is not too low from the perspective of the heat resistance performance of the adhesive sheet and the suppression of contamination of the substrate.

[0206] Non-limiting examples of compounds that can be selected as plasticizing materials include: compounds that can be used as monomers (m1) (e.g., (meth)acrylates having aromatic rings such as benzyl groups, phenoxy groups, naphthyl groups, monomers having a fluorene structure, monomers having a dinaphthothiophene structure, monomers having a dibenzothiophene structure, etc.); oligomers containing compounds that can be used as monomers (m1) as monomer units; compounds having a structure in which, excluding the portion having an ethylenically unsaturated group from the compounds that can be used as monomers (m1), hydrogen atoms or groups not having an ethylenically unsaturated group are substituted (e.g., 3-phenoxybenzyl alcohol); etc. In the oligomer containing compounds that can be used as monomers (m1) as monomer units, low Tg monomers such as n-butyl acrylate or 2-ethylhexyl acrylate may be copolymerized for the purpose of improving flexibility. As a plasticizing material, one or more of known plasticizers (e.g., phthalic acid esters, terephthalic acid esters, adipic acid esters, adipic acid polyesters, glycol benzoate esters, etc.) may be used.

[0207] In some embodiments, as a plasticizing material, an organic material having a refractive index of approximately 1.50 or higher (more preferably 1.53 or higher) may be preferably used. Specific examples of compounds that may be options for plasticizing materials include diethylene glycol dibenzoate (refractive index 1.55), dipropylene glycol dibenzoate (refractive index 1.54), 3-phenoxytoluene (refractive index 1.57), 3-ethyl biphenyl (refractive index 1.59), 3-methoxybiphenyl (refractive index 1.61), 4-methoxybiphenyl (refractive index 1.57), polyethylene glycol dibenzoate, 3-phenoxybenzyl alcohol (refractive index 1.59), triphenyl phosphate (refractive index 1.56), benzyl benzoate (refractive index 1.57), 4-(tert-butyl)phenyldiphenyl phosphate (refractive index 1.56), trimethylphenyl phosphate (refractive index 1.55), butylbenzyl phthalate (refractive index 1.54). Examples include, but are not limited to, rosin methyl ester (refractive index 1.53), alkylbenzyl phthalate (refractive index 1.53), butyl(phenylsulfonyl)amine (refractive index 1.53), trimethyltrimellitate (refractive index 1.52), benzyl phthalate (refractive index 1.52), 2-ethylhexyl diphenyl phosphate (refractive index 1.51), tris(2,4-di-tert-butylphenyl) phosphoric acid. From the perspective of refractive index and compatibility, for example, diethylene glycol dibenzoate may be preferably employed. The upper limit of the refractive index of the plasticizing material is not particularly limited and may be, for example, 3.00 or less. In several embodiments, from the perspective of ease of preparation of the adhesive composition or compatibility within the adhesive, the refractive index of the plasticizing material is preferably 2.50 or less, advantageously 2.00 or less, and may be 1.90 or less, 1.80 or less, or 1.70 or less.

[0208] In addition, the refractive index of the plasticized material is measured using an Abbe refractive index meter, just like the refractive index of the monomer, under conditions of a measurement wavelength of 589 nm and a measurement temperature of 25°C. If a nominal value of the refractive index at 25°C is provided by the manufacturer or others, that nominal value may be adopted.

[0209] In the embodiment of using a plasticizing material, the amount of plasticizing material used per 100 parts by weight of base polymer is not particularly limited and can be set according to the purpose. From the perspective of increasing the plasticizing effect, the amount of plasticizing material used per 100 parts by weight of base polymer may, for example, be 0.1 parts by weight or more, or 0.5 parts by weight or more; from the perspective of obtaining a higher plasticizing effect, it is preferable to make it 1 part by weight or more, more preferable to make it 3 parts by weight or more, or 5 parts by weight or more, 7 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, or 20 parts by weight or more. In addition, from the perspective of achieving a good balance of high refractive index, transparency, and plasticizing effects of the adhesive, the amount of plasticizing material used per 100 parts by weight of base polymer is appropriately about 100 parts by weight or less, preferably 80 parts by weight or less, more preferably 60 parts by weight or less, and may be 45 parts by weight or less, 35 parts by weight or less, or 25 parts by weight or less. In several embodiments that place greater emphasis on adhesive properties or optical properties, the amount of plasticizing material used per 100 parts by weight of base polymer may be 15 parts by weight or less, 10 parts by weight or less, or 5 parts by weight or less.

[0210] (Leveling agent)

[0211] In several embodiments, the adhesive composition used to form the adhesive layer may contain a leveling agent as needed for purposes such as improving the appearance of the adhesive layer formed by the composition (e.g., improving the uniformity of thickness) or improving the coating properties of the adhesive composition. Non-limiting examples of leveling agents include acrylic leveling agents, fluorine-based leveling agents, silicone-based leveling agents, etc. The leveling agent may be selected from commercially available leveling agents and used according to commercial methods.

[0212] In several embodiments, as the leveling agent, a polymer (hereinafter also referred to as “polymer (B)”) which is a polymer of a monomer having a polyorganosiloxane backbone (hereinafter also referred to as “monomer S1”) and a monomer raw material (hereinafter also referred to as “monomer raw material B”) containing an acrylic monomer may be preferably used. Polymer (B) may be a copolymer of monomer S1 and an acrylic monomer. Polymer (B) may be used as a single type or in combination of two or more types.

[0213] As monomer S1, any monomer containing a polyorganosiloxane backbone can be used, without being particularly limited. As monomer S1, a structure having a polymerizable reactive group at one end can be preferably used. Among these, monomer S1 having a structure having a polymerizable reactive group at one end and not having a functional group at the other end that causes a cross-linking reaction with a base polymer (referring to the base polymer of the adhesive composition to which the leveling agent is incorporated; for example, an acrylic polymer) can be preferably adopted. As a commercially available product, for example, the one-end reactive silicone oil manufactured by Shin-Etsu Chemical Co., Ltd. (e.g., product numbers X-22-174ASX, X-22-2426, X-22-2475, KF-2012, etc.) can be cited. Monomer S1 can be used as a single type or in combination of two or more types.

[0214] The functional group equivalent of monomer S1 may be, for example, approximately 100 g / mol to 30,000 g / mol. In some preferred embodiments, the functional group equivalent may be, for example, 500 g / mol or more, 800 g / mol or more, 1,500 g / mol or more, or 2,000 g / mol or more. Additionally, the functional group equivalent may be, for example, 20,000 g / mol or less, less than 10,000 g / mol, 7,000 g / mol or less, or 5,500 g / mol or less. If the functional group equivalent of monomer S1 is within the above range, a good leveling effect is easily exhibited.

[0215] In addition, when using two or more types of monomers with different functional group equivalents as monomer S1, the functional group equivalent of monomer S1 may be the sum of the products of the functional group equivalent of each type of monomer and the weight fraction of the corresponding monomer.

[0216] Here, "functional group equivalent" refers to the weight of the main backbone (e.g., polydimethylsiloxane) attached per functional group. Regarding the notation unit g / mol, it is converted to 1 mol of functional group. The functional group equivalent of monomer S1 is, for example, based on nuclear magnetic resonance (NMR). 1 It can be calculated from the spectral intensity of H-NMR (proton NMR). 1 The calculation of the functional group equivalent (g / mol) of monomer S1 based on the spectral intensity of H-NMR is, 1 Based on a general structural analysis method regarding H-NMR spectrum analysis, if necessary, it can be done by referring to the description in Japanese Patent Publication No. 5951153. In the functional group equivalent of monomer S1, the functional group refers to a polymerizable functional group (e.g., an ethylenically unsaturated group such as a (meth)acryloyl group, a vinyl group, or an allyl group).

[0217] The content of monomer S1 in monomer raw material B may be an appropriate value within a range where the desired effect is achieved using the monomer S1, and is not limited to a specific range. In some embodiments, the content of monomer S1 in monomer raw material B may be, for example, 5 to 60 weight%, 10 to 50 weight%, or 15 to 40 weight%.

[0218] Monomer raw material B comprises, in addition to monomer S1, an acrylic monomer capable of copolymerizing with monomer S1. This improves the compatibility of the polymer (B) within the adhesive layer. An example of an acrylic monomer that can be used for monomer raw material B is an alkyl acrylate ester. The term "alkyl" as used herein refers to a chain-like (including straight and branched chain) alkyl group and does not include the alicyclic hydrocarbon groups described later. In several embodiments, monomer raw material B is (meth)acrylic acid C 4-12 Alkyl ester (preferably (meth)acrylic acid C) 4-10 Alkyl esters, e.g., (meth)acrylic acid C 6-10 It may contain at least one type of alkyl ester. In some other embodiments, monomer raw material B is methacrylic acid C 1-18 Alkyl ester (preferably methacrylic acid C) 1-14 Alkyl esters, e.g., methacrylic acid C 1-10 It may contain at least one type of alkyl ester. Monomer raw material B may include one or more types selected from, for example, methyl methacrylate (MMA), n-butyl methacrylate (BMA), and 2-ethylhexyl methacrylate (2EHMA) as acrylic monomers.

[0219] As another example of the above-mentioned acrylic monomer, (meth)acrylic acid esters having alicyclic hydrocarbon groups may be used. For example, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclofentanyl (meth)acrylate, 1-adamantyl (meth)acrylate, etc. may be used. (meth)acrylic acid esters having alicyclic hydrocarbon groups may not be used.

[0220] The content of the (meth)acrylic acid alkyl ester and the (meth)acrylic acid ester having an alicyclic hydrocarbon group in monomer raw material B may, for example, be 10% by weight or more and 95% by weight or less, 20% by weight or more and 95% by weight or less, 30% by weight or more and 90% by weight or less, 40% by weight or more and 90% by weight or less, and 50% by weight or more and 85% by weight or less.

[0221] Other examples of monomers that can be included in monomer raw material B together with monomer S1 include monomers that can be used in acrylic polymers, such as the carboxyl group-containing monomer, acid anhydride group-containing monomer, hydroxyl group-containing monomer, epoxy group-containing monomer, cyano group-containing monomer, isocyanate group-containing monomer, amide group-containing monomer, monomer having a nitrogen atom-containing ring, (meth)acrylate aminoalkyls, vinyl esters, vinyl ethers, olefins, (meth)acrylic acid esters having aromatic hydrocarbon groups, (meth)acrylates containing halogen atoms, etc.

[0222] The Mw of the polymer (B) may, for example, be 5,000 or more, preferably 10,000 or more, and may be 15,000 or more. Additionally, the Mw of the polymer (B) may, for example, be 200,000 or less, preferably 100,000 or less, may be 50,000 or less, and may be 30,000 or less. By setting the Mw of the polymer (B) to an appropriate range, suitable compatibility and leveling properties can be achieved.

[0223] The polymer (B) can be produced by polymerizing, for example, the monomer described above by a known method such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, or photopolymerization.

[0224] To adjust the molecular weight of the polymer (B), a chain transfer agent may be used as needed. Examples of chain transfer agents used include compounds having a mercapto group such as t-dodecyl mercaptan, mercaptoethanol, and α-thioglycerol; thioglycolic acid esters such as thioglycolic acid and methyl thioglycolate; and α-methylstyrene dimer. The amount of chain transfer agent used is not particularly limited and can be appropriately set to obtain a polymer (B) having a desired molecular weight. In some embodiments, the amount of chain transfer agent used per 100 parts by weight of monomer may be, for example, 0.1 to 5 parts by weight, 0.2 to 3 parts by weight, or 0.5 to 2 parts by weight.

[0225] The amount of polymer (B) used per 100 parts by weight of base polymer (e.g., acrylic polymer) can be, for example, 0.001 parts by weight or more, and for the sake of obtaining a higher usage effect, it can be 0.01 parts by weight or more, or 0.03 parts by weight or more. In addition, the amount of polymer (B) used can be, for example, 3 parts by weight or less, and for the sake of reducing the influence on the refractive index, it is appropriate to be 1 part by weight or less, 0.5 parts by weight or less, or 0.1 parts by weight or less.

[0226] (Inorganic particles)

[0227] The technology disclosed herein can preferably be implemented in an embodiment in which inorganic particles as refractive index enhancers are not substantially used. However, in some embodiments of the adhesive sheets disclosed herein, the use of inorganic particles as refractive index enhancers may be permitted to the extent that desired optical properties (total light transmittance, haze value) are satisfied and the properties as an adhesive are not significantly impaired. Examples of inorganic particles that can be used as refractive index enhancers include inorganic particles composed of inorganic oxides (specifically metal oxides) such as titania (titanium oxide, TiO2), zirconia (zirconium oxide, ZrO2), aluminum oxide, zinc oxide, tin oxide, copper oxide, barium titanate, niobium oxide (Nb2O5, etc.). The average particle size of the inorganic particles (referring to the 50% volume average particle size based on laser scattering and diffraction methods) can be selected from a range of, for example, 10 nm to 100 nm. In addition, the refractive index of the inorganic particles is measured using a commercially available spectroscopic ellipsometer on a monolayer of the material constituting the inorganic particles (with a film thickness capable of measuring the refractive index) under conditions of a measurement wavelength of 589 nm and a measurement temperature of 23°C. As the spectroscopic ellipsometer, for example, the product name "EC-400" (manufactured by JA. Woolam) or an equivalent product is used. When using inorganic particles as a refractive index improver, the amount used is preferably less than 5 parts by weight per 100 parts by weight of the base polymer, and more preferably less than 1 part by weight. Additive (H RO In the embodiment using ), the amount of the inorganic particle used is, on a weight basis, the additive (H RO It is desirable to keep the amount of ) used at 2 times or less, and more desirable to keep it at 1 time or 0.5 times or less.

[0228] (Crosslinking agent)

[0229] In the technology disclosed herein, the adhesive composition used for forming the adhesive layer may contain a crosslinking agent as needed for purposes such as adjusting the cohesive force of the adhesive. As a crosslinking agent, crosslinking agents known in the field of adhesives, such as isocyanate-based crosslinking agents, epoxy-based crosslinking agents, aziridine-based crosslinking agents, oxazoline-based crosslinking agents, melamine-based resins, and metal chelate-based crosslinking agents, may be used. Among these, isocyanate-based crosslinking agents may be preferably employed. As another example of a crosslinking agent, a monomer having two or more ethylenically unsaturated groups within one molecule, i.e., a polyfunctional monomer, may be cited. The crosslinking agent may be used as a single type or in combination of two or more types.

[0230] As isocyanate-based crosslinking agents, isocyanate compounds with two or more functional groups may be used, for example, aliphatic polyisocyanates such as trimethylene diisocyanate, butylene diisocyanate, hexamethylene diisocyanate (HDI), and dimer acid diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate (IPDI), and 1,3-bis(isocyanatomethyl)cyclohexane; aromatic isocyanates such as 2,4-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate (XDI); Examples include polyisocyanate modified compounds in which the above isocyanate compound is modified by allophanate bonds, biuret bonds, isocyanurate bonds, urethdione bonds, urea bonds, carbodiimide bonds, uretonimine bonds, oxadiazinetrione bonds, etc. Examples of commercially available products include the trade names Takenate 300S, Takenate 500, Takenate 600, Takenate D165N, Takenate D178N (all manufactured by Takeda Yakuhin Kogyo Co., Ltd.), Sumidur T80, Sumidur L, Desmodur N3400 (all manufactured by Sumika Bayer Urethane Co., Ltd.), Mylionate MR, Mylionate MT, Coronate L, Coronate HL, Coronate HX (all manufactured by Dosoh Co., Ltd.). The isocyanate compound may be used as a single type or in combination of two or more types. It is acceptable to use a combination of a difunctional isocyanate compound and a trifunctional or higher isocyanate compound.

[0231] Examples of epoxy crosslinking agents include bisphenol A, epichlorohydrin-type epoxy resin, ethylene glycidyl ether, polyethylene glycol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, 1,6-hexanediol glycidyl ether, trimethylolpropane triglycidyl ether, diglycidylaniline, diamine glycidylamine, N,N,N',N'-tetraglycidyl-m-xylylenediamine, and 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane. These may be used individually or in combination of two or more.

[0232] As polyfunctional monomers, for example, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl(meth)acrylate, vinyl(meth)acrylate, divinylbenzene, bisphenoxyethanol fluorene di(meth)acrylate, and bisphenol A Examples include di(meth)acrylates, epoxy acrylates, polyester acrylates, urethane acrylates, butyldiol (meth)acrylates, hexyldiol di(meth)acrylates, etc. Polyfunctional monomers may be used individually or in combination of two or more types.

[0233] When using a crosslinking agent (which may be a polyfunctional monomer), the amount used is not particularly limited and, for example, can be in the range of about 0.001 to 5.0 parts by weight per 100 parts by weight of base polymer. In some embodiments, from the perspective of improving the flexibility of the adhesive, the amount of crosslinking agent used per 100 parts by weight of base polymer is preferably 3.0 parts by weight or less, more preferably 2.0 parts by weight or less, and may be 1.0 parts by weight or less, 0.5 parts by weight or less, or 0.2 parts by weight or less. In addition, from the perspective of appropriately exhibiting the effect of using the crosslinking agent, in some embodiments, the amount of crosslinking agent used per 100 parts by weight of base polymer may, for example, be 0.005 parts by weight or more, 0.01 parts by weight or more, 0.05 parts by weight or more, or 0.08 parts by weight or more.

[0234] To carry out the crosslinking reaction more effectively, a crosslinking catalyst may be used. Examples of crosslinking catalysts include metal-based crosslinking catalysts such as tetra-n-butyl titanate, tetraisopropyl titanate, ferric nasem, butyl tin oxide, and dioctyl tin dilaurate. Among these, tin-based crosslinking catalysts such as dioctyl tin dilaurate are preferred. The amount of crosslinking catalyst used is not particularly limited. Considering the balance between the speed of the crosslinking reaction and the pot life of the adhesive composition, the amount of crosslinking catalyst used per 100 parts by weight of base polymer can be, for example, in a range of approximately 0.0001 parts by weight or more and 1 part by weight or less, and it is preferable to have a range of 0.001 parts by weight or more and 0.5 parts by weight or less.

[0235] The adhesive composition may contain a compound that generates keto-enol tautomerism as a crosslinking retardant. By doing so, the effect of extending the pot life of the adhesive composition can be realized. For example, in an adhesive composition containing an isocyanate-based crosslinking agent, a compound that generates keto-enol tautomerism can be preferably used. Various β-dicarbonyl compounds can be used as compounds that generate keto-enol tautomerism. For example, β-diketones (acetylacetone, 2,4-hexanedione, etc.) or acetoacetic acid esters (methyl acetoacetate, ethyl acetoacetate, etc.) can be preferably employed. The compounds that generate keto-enol tautomerism may be used as a single type or in combination of two or more types. The amount of compound that generates keto-enol tautomerity can be, for example, 0.1 parts by weight or more and 20 parts by weight or less per 100 parts by weight of base polymer, 0.5 parts by weight or more and 10 parts by weight or less, or 1 part by weight or more and 5 parts by weight or less.

[0236] (Tackifier)

[0237] The adhesive layer in the technology disclosed herein may contain a tackifier. As a tackifier, known tackifier resins such as rosin-based tackifier resins, terpene-based tackifier resins, phenol-based tackifier resins, hydrocarbon-based tackifier resins, ketone-based tackifier resins, polyamide-based tackifier resins, epoxy-based tackifier resins, and elastomer-based tackifier resins may be used. These may be used individually or in combination of two or more types. The amount of tackifier resin used is not particularly limited and can be set to ensure appropriate adhesive performance according to the purpose or application. In several embodiments, from the perspective of refractive index or transparency, the amount of tackifier used is preferably 30 parts by weight or less, preferably 10 parts by weight or less, and more preferably 5 parts by weight or less per 100 parts by weight of the base polymer of the adhesive layer. The technology disclosed herein may preferably be implemented in an embodiment without using a tackifier.

[0238] (Other additives)

[0239] In the technology disclosed herein, the adhesive composition used for forming the adhesive layer may, if necessary, include known additives that can be used in adhesive compositions, such as plasticizers, softeners, colorants, antistatic agents, anti-aging agents, UV absorbers, antioxidants, light stabilizers, and preservatives, to the extent that the effects of the present invention are not significantly impaired. As such various additives are conventionally known and may be used according to commercial practices and do not particularly characterize the present invention, a detailed description is omitted.

[0240] (Fabrication of the adhesive layer)

[0241] In the technology disclosed herein, the adhesive constituting the adhesive layer may be an adhesive formed by curing an adhesive composition of the form of a solvent type, active energy beam curable type, water-dispersible type, hot-melt type, etc., by drying, crosslinking, polymerization, cooling, etc., that is, a cured product of said adhesive composition. The curing means of the adhesive composition (e.g., drying, crosslinking, polymerization, cooling, etc.) may be applied as a single type, or two or more types may be applied simultaneously or in multiple stages. In the case of a solvent-type adhesive composition, the adhesive can typically be formed by drying (preferably also crosslinking) the composition. In the case of an active energy beam curable adhesive composition, the adhesive is typically formed by carrying out a polymerization reaction and / or a crosslinking reaction by irradiating an active energy beam. If drying is required in the case of an active energy beam curable adhesive composition, the active energy beam may be irradiated after drying.

[0242] The adhesive layer of the adhesive sheet disclosed herein can be formed by applying (e.g., coating) an adhesive composition to a suitable surface and then curing the composition. The coating of the adhesive composition can be carried out using a conventional coater, such as a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a bar coater, a knife coater, or a spray coater.

[0243] The adhesive layer of the adhesive sheet disclosed herein may be an adhesive layer having post-curing properties or an adhesive layer not having post-curing properties. Here, an adhesive layer having post-curing properties refers to an adhesive layer that can be further cured by irradiation with heat or active energy rays (e.g., ultraviolet rays). Examples of an adhesive layer having post-curing properties include an adhesive layer having unreacted ethylenically unsaturated groups in the side chains of a base polymer or an adhesive layer containing unreacted polyfunctional monomers. In some embodiments, it is preferable that the adhesive layer does not have post-curing properties. Since an adhesive layer not having post-curing properties does not cause dimensional changes associated with the post-curing reaction (i.e., has good dimensional stability), it is easy to suppress warping of the adhesive sheet or the substrate to which the adhesive sheet is attached. The fact that dimensional changes due to post-curing (e.g., curing shrinkage) do not occur can also be advantageous from the perspective of suppressing optical distortion of the adhesive layer.

[0244] The thickness of the adhesive layer is not particularly limited and, for example, can be 3 μm or more, and is preferably 5 μm or more. With an adhesive layer having a thickness of 5 μm or more, good adhesive properties are easily obtained. In addition, an adhesive layer of such thickness absorbs irregularities that may exist on the surface of the substrate, making it easy to bond to the substrate with good adhesion. It is also desirable for the thickness of the adhesive layer to be 5 μm or more from the perspective of preventing discoloration or color non-uniformity caused by light interference. In some embodiments, the thickness of the adhesive layer may be 10 μm or more, 20 μm or more, 30 μm or more, 50 μm or more, 70 μm or more, or 85 μm or more. In addition, in some embodiments, the thickness of the adhesive layer may be, for example, 300 μm or less, 250 μm or less, 200 μm or less, 150 μm or less, or 120 μm or less. Not having a thickness of the adhesive layer that is too large can be advantageous from the perspective of thinning the adhesive sheet. The technology disclosed herein may be preferably implemented, for example, in an embodiment where the thickness of the adhesive layer is in the range of 3 μm to 200 μm (more preferably 5 μm to 100 μm). Furthermore, in the case of an adhesive sheet having a first adhesive layer and a second adhesive layer on a first surface and a second surface of a substrate, the thickness of the adhesive layer described above may be applied to at least the thickness of the first adhesive layer. The thickness of the second adhesive layer may also be selected from the same range. In addition, in a double-sided adhesive sheet without a substrate formed by an adhesive layer, the thickness of the adhesive layer becomes the thickness of the adhesive sheet.

[0245] (Peel strength)

[0246] In some embodiments of the adhesive sheet disclosed herein, the peel strength of the adhesive sheet against a glass plate is suitably approximately 1.0 N / 25 mm or more (e.g., 1.5 N / 25 mm or more), preferably 2 N / 25 mm or more, more preferably 3 N / 25 mm or more, and may be 4 N / 25 mm or more, 6 N / 25 mm or more, 8 N / 25 mm or more, 10 N / 25 mm or more, or 12 N / 25 mm or more. The upper limit of the peel strength is not particularly limited and may be, for example, 30 N / 25 mm or less, 25 N / 25 mm or less, or 20 N / 25 mm or less.

[0247] Here, the peel strength is determined by pressing the material onto an alkali glass plate as a substrate, leaving it for 30 minutes in an environment of 23°C and 50%RH, then placing it into a pressurized degassing device (autoclave) and performing autoclave treatment for 30 minutes under conditions of a temperature of 50°C and a pressure of 0.5 MPa, and then leaving it for 24 hours under an atmosphere of 23°C and 50%RH, and finally measuring the 180° peel adhesion strength under conditions of a peel angle of 180° and a tensile speed of 300 mm / min. In the measurement, if necessary, a suitable backing material (e.g., a polyethylene terephthalate (PET) film with a thickness of about 25 μm to 50 μm) may be attached to the adhesive sheet to be measured to reinforce it. More specifically, the peel strength can be measured in accordance with the method described in the examples described below.

[0248] When the adhesive sheet disclosed herein is in the form of a double-sided adhesive sheet having a first adhesive surface and a second adhesive surface, in several embodiments, the peel strength described above is preferably applied to at least the first adhesive surface, and more preferably to both the first adhesive surface and the second adhesive surface. The peel strength of the first adhesive surface against a glass plate and the peel strength of the second adhesive surface against glass may be of the same degree or may be different.

[0249] <Support Information>

[0250] An adhesive sheet according to several embodiments may be in the form of an adhesive sheet having a substrate having an adhesive layer on one or both sides of a supporting substrate. The material of the supporting substrate is not particularly limited and can be appropriately selected depending on the purpose of use or mode of use of the adhesive sheet. Non-limiting examples of substrates that can be used include: a polyolefin film mainly composed of a polyolefin such as polypropylene (PP) or ethylene-propylene copolymer; a polyester film mainly composed of a polyester such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), or polyethylene naphthalate (PEN); a plastic film mainly composed of polyvinyl chloride; a foam sheet made of a foam such as polyurethane foam, polyethylene (PE) foam, or polychloroprene foam; Examples include woven and nonwoven fabrics made by using various fibrous materials (such as natural fibers like linen and cotton, synthetic fibers like polyester and vinylon, semi-synthetic fibers like acetate, etc.) either alone or in a blend; paper products such as washi, high-quality paper, kraft paper, and crepe paper; and metal foils such as aluminum foil and copper foil. A substrate with a composite composition of these materials may also be used. Examples of such composite substrates include a substrate with a structure in which a metal foil and the above-mentioned plastic film are laminated, and a plastic substrate reinforced with inorganic fibers such as glass cloth.

[0251] In several embodiments, various film substrates may be preferably used. The film substrate may be a porous substrate, such as a foam film or a non-woven sheet, a non-porous substrate, or a substrate having a structure in which a porous layer and a non-porous layer are laminated. In several embodiments, the film substrate may preferably include a resin film capable of maintaining its shape independently (self-supporting or non-dependent) as a base film. Here, "resin film" refers to a resin film having a non-porous structure and, typically, substantially not containing bubbles (voidless). Therefore, the resin film is a concept distinct from foam films or non-woven fabrics. The resin film may preferably be capable of maintaining its shape independently (self-supporting or non-dependent). The resin film may have a single-layer structure or a multi-layer structure of two or more layers (e.g., a three-layer structure).

[0252] Materials constituting the resin film include, for example, polyester resins with polyester as the main component, such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyethylene naphthalate (PEN); polyolefin resins with polyolefin as the main component, such as polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, and ethylene-butene copolymer; cellulose resins such as triacetylcellulose; acetate resins; polysulfone resins; polyethersulfone resins; polycarbonate resins; polyamide (PA) resins such as nylon 6, nylon 66, and partially aromatic polyamide; polyimide (PI) resins; transparent polyimide resin; polyamideimide (PAI); polyetheretherketone (PEEK); polyethersulfone (PES); norbornene resins; cyclic polyolefin resins; (meth)acrylic resins; and polyvinyl chloride resins. Examples include polyvinylidene chloride-based resins, polystyrene-based resins, polyvinyl alcohol-based resins, ethylene-vinyl acetate copolymer resins, ethylene-vinyl alcohol copolymer resins, polyarylate-based resins, polyphenylene sulfide (PPS)-based resins, polyurethane (PU), ethylene-vinyl acetate copolymer (EVA), polytetrafluoroethylene (PTFE), and fluorinated resins such as fluorinated polyimide.

[0253] The resin film may be formed using a resin material containing only one type of such resin, or it may be formed using a resin material in which two or more types are blended. The resin film may be unoriented or oriented (e.g., uniaxial or biaxial). For example, PET film, PBT film, PEN film, unoriented polypropylene (CPP) film, biaxially oriented polypropylene (OPP) film, low-density polyethylene (LDPE) film, linear low-density polyethylene (LLDPE) film, PP / PE blend film, etc., may be preferably used. Examples of resin films preferred in terms of strength or dimensional stability include PET film, PEN film, PPS film, and PEEK film. PET film and PPS film are particularly preferred in terms of ease of availability, and among them, PET film is preferred.

[0254] In the resin film, known additives such as light stabilizers, antioxidants, antistatic agents, coloring agents (dyes, pigments, etc.), fillers, slip agents, and anti-blocking agents may be incorporated as needed, within a range where the effects of the present invention are not significantly impaired. The amount of additives incorporated is not particularly limited and can be appropriately set according to the use of the adhesive sheet, etc.

[0255] The method of manufacturing the resin film is not particularly limited. For example, conventionally known general resin film molding methods such as extrusion molding, inflation molding, T-die casting, and calender roll molding may be appropriately employed.

[0256] The above-mentioned material may be substantially composed of such a base film. Alternatively, the above-mentioned material may include an auxiliary layer in addition to the base film. Examples of the above-mentioned auxiliary layer include an optical property adjusting layer (e.g., a coloring layer, an anti-reflective layer), a printing layer or a laminate layer for imparting a desired appearance to the material, an antistatic layer, a primer layer, a release layer, and other surface treatment layers.

[0257] In several embodiments, a light-transmitting substrate (hereinafter also referred to as a light-transmitting substrate) may be preferably employed as the supporting substrate. This makes it possible to construct an adhesive sheet having a light-transmitting substrate. The total light transmittance of the light-transmitting substrate may, for example, exceed 50% or be 70% or more. In several preferred embodiments, the total light transmittance of the supporting substrate is 80% or more, more preferably 90% or more, and may be 95% or more (for example, 95 to 100%). The above total light transmittance is measured using a commercially available transmittance meter in accordance with JIS K 7136:2000. As the transmittance meter, the product name "HAZEMETER HM-150" manufactured by Kijutsu Genkyujo of Shikisai Murakami or an equivalent product thereof is used. As a suitable example of the above light-transmitting substrate, a resin film having light-transmitting properties may be cited. The above light-transmitting substrate may also be an optical film.

[0258] The thickness of the substrate is not particularly limited and can be selected according to the purpose or mode of use of the adhesive sheet. The thickness of the substrate may, for example, be 500 μm or less, and from the perspective of the handling and processability of the adhesive sheet, it is preferable to be 300 μm or less, 150 μm or less, 100 μm or less, 50 μm or less, 25 μm or less, or 10 μm or less. As the thickness of the substrate decreases, the conformability to the surface shape of the substrate tends to improve. In addition, from the perspective of handling and processability, the thickness of the substrate may, for example, be 2 μm or more, 10 μm or more, or 25 μm or more.

[0259] On the side of the substrate where the adhesive layer is laminated, conventionally known surface treatments such as corona discharge treatment, plasma treatment, UV irradiation treatment, acid treatment, alkali treatment, or the formation of an undercoat layer by applying a primer may be performed as needed. Such surface treatments may be treatments intended to improve the anchoring properties of the adhesive layer to the substrate. The composition of the primer used to form the undercoat layer is not particularly limited and can be appropriately selected from known ones. The thickness of the undercoat layer is not particularly limited, but typically, about 0.01 μm to 1 μm is suitable, and about 0.1 μm to 1 μm is preferred. Other treatments that may be performed on the substrate as needed include antistatic layer formation treatment, coloring layer formation treatment, and printing treatment. These treatments may be applied alone or in combination.

[0260] In the case where the adhesive sheet disclosed herein is in the form of an adhesive sheet having a substrate, the thickness of the adhesive sheet may be, for example, 1000 μm or less, 350 μm or less, 200 μm or less, 120 μm or less, 75 μm or less, or 50 μm or less. In addition, the thickness of the adhesive sheet may be, for example, 10 μm or more, 25 μm or more, 80 μm or more, or 130 μm or more from the perspective of handling, etc.

[0261] In addition, the thickness of the adhesive sheet refers to the thickness of the portion attached to the substrate. For example, in the adhesive sheet (1) of the configuration shown in FIG. 1, it refers to the thickness from the first surface (adhesive surface) (10A) of the adhesive layer to the second surface (20B) of the supporting substrate, and the thickness of the release liner (30) is not included.

[0262] <Adhesive sheet equipped with a release liner>

[0263] The adhesive sheet disclosed herein may take the form of an adhesive product in which the surface (adhesive surface) of the adhesive layer is in contact with the release surface of a release liner. Accordingly, by this specification, an adhesive sheet (adhesive product) is provided that comprises a release liner having a release surface in contact with the adhesive surface of any of the adhesive sheets disclosed herein.

[0264] As for the release liner, it is not particularly limited, and for example, a release liner having a release treatment layer on a release liner substrate such as a resin film or paper (which may be paper laminated with a resin such as polyethylene), or a release liner made of a resin film formed by a low-adhesion material such as a fluorine-based polymer (polytetrafluoroethylene, etc.) or a polyolefin-based resin (polyethylene, polypropylene, etc.) may be used. The release treatment layer may be formed by surface treating the release liner substrate with a release treatment agent. The release treatment agent may be a known release treatment agent such as a silicone-based release treatment agent, a long-chain alkyl-based release treatment agent, a fluorine-based release treatment agent, or molybdenum sulfide (IV). In several embodiments, a release liner having a release treatment layer formed by a silicone-based release treatment agent may be preferably employed. The thickness or method of forming the release treatment layer is not particularly limited and can be set so that appropriate release properties are exhibited on the adhesive side surface of the release liner.

[0265] In several embodiments, a release liner (hereinafter also referred to as a release film) having a release treatment layer on a resin film (hereinafter also referred to as a release film substrate) as a release liner substrate may be preferably employed from the perspective of the smoothness of the adhesive surface. Various plastic films may be used as the release film substrate. In this specification, a plastic film is typically a non-porous sheet and is a concept distinct from, for example, non-woven fabric (i.e., not including non-woven fabric).

[0266] Examples of materials for the above plastic film include polyester resins such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyethylene naphthalate (PEN); polyolefin resins such as polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, and ethylene-butene copolymer; cellulose resins such as triacetylcellulose; acetate resins; polysulfone resins; polyethersulfone resins; polycarbonate resins; polyamide resins; polyimide resins; norbornene resins; cyclic polyolefin resins; (meth)acrylic resins; polyvinyl chloride resins; polyvinylidene chloride resins; polystyrene resins; polyvinyl alcohol resins; ethylene-vinyl acetate copolymer resins; ethylene-vinyl alcohol copolymer resins; polyarylate resins; and polyphenylene sulfide resins. A release film substrate formed from any one of these resins or a mixture of two or more of them may be used. Among these, a preferred release film substrate is a polyester resin film formed from a polyester resin (e.g., a PET film).

[0267] The plastic film used as the release film substrate described above may be any of a non-oriented film, a uniaxially oriented film, or a biaxially oriented film. In addition, the plastic film may have a single-layer structure or a multilayer structure including two or more sublayers. The plastic film may contain known additives that can be used as release film substrates for adhesive sheets, such as antioxidants, anti-aging agents, heat stabilizers, light stabilizers, UV absorbers, coloring agents such as pigments or dyes, lubricants, fillers, antistatic agents, and nucleating agents. In the case of a multilayer plastic film, each additive may be incorporated into all sublayers or only into some sublayers.

[0268] In some preferred embodiments, the release film substrate (typically a plastic film) may preferably be used such that the content of particles (e.g., pigments, lubricants, fillers, etc.) in the layer on the release side is limited, or that such particles are substantially not included. Here, "substantially not included" means that the amount of particles (e.g., inorganic particles) in the layer is less than 1 weight%, and preferably less than 0.1 weight% (e.g., 0 to 0.01 weight%). A release film having such a release film substrate is prone to having a low arithmetic mean roughness Ra or maximum height Rz of the release surface. When the release film substrate (typically a plastic film) has a multilayer structure, the particle content in the layer on the release side may be 1 / 10 or less (e.g., 1 / 50 or less) of the particle content in layers other than the layer on the release side.

[0269] In an adhesive sheet having a release liner having a form having a release liner on each of a first adhesive surface and a second adhesive surface, the release liner disposed on one adhesive surface (hereinafter also referred to as the release liner of one side) and the release liner disposed on the other adhesive surface (hereinafter also referred to as the release liner of the other side) may have the same material and composition, or may have different material and composition.

[0270] The thickness of the release liner (preferably a release film) is not particularly limited and may be, for example, about 10 μm to 500 μm. From the perspective of strength or dimensional stability of the release liner, the thickness of the release liner is suitable to be 20 μm or more, preferably 30 μm or more, may be 35 μm or more, may be 40 μm or more, or may be 45 μm or more. In addition, from the perspective of handling properties of the release liner (e.g., ease of winding), the thickness of the release liner is suitable to be 300 μm or less, preferably 250 μm or less, may be 200 μm or less, may be 150 μm or less, or may be 130 μm or less. In several preferred embodiments, the thickness of the release liner may be approximately 125 μm or less, may be approximately 115 μm or less, may be approximately 105 μm or less, may be approximately 90 μm or less, or may be approximately 70 μm or less. By making the thickness of the release liner less than or equal to a predetermined value, it becomes difficult to form winding marks when in a roll shape, and removal from the adhesive sheet becomes smooth, making it easy to obtain high surface smoothness on the adhesive surface after removing the release liner.

[0271] In an embodiment having one release liner and the other release liner, the thicknesses of the release liners may be the same or different. In some embodiments, it is preferable for one release liner and the other release liner to have different thicknesses from the perspective of release workability, etc. For example, it is preferable that the thickness of the thicker release liner be approximately 1.1 times or more (for example, approximately 1.25 times or more. The upper limit is not particularly limited, but for example, 5 times or less) the thickness of the thinner release liner.

[0272] (Arithmetic mean roughness Ra of the adhesive side surface)

[0273] In some embodiments, the release liner (preferably a release film) is preferably limited to an arithmetic mean roughness Ra of the adhesive-side surface to a predetermined value or less (e.g., approximately 100 nm or less, further less than 50 nm) from the perspective of realizing an adhesive surface having high surface smoothness. In some embodiments, the arithmetic mean roughness Ra of the adhesive-side surface of the release liner is preferably, for example, approximately 30 nm or less, more preferably approximately 25 nm or less, may be approximately 20 nm or less, or may be approximately 18 nm or less. Furthermore, in some embodiments, from the perspective of ease of manufacturing or handling of the release liner, the arithmetic mean roughness Ra may be, for example, approximately 5 nm or more, approximately 10 nm or more, or approximately 15 nm or more. In an adhesive sheet having a release liner configured such that a release liner is disposed on each of a first adhesive surface and a second adhesive surface, it is preferable that the adhesive surface-side surfaces of both release liners satisfy the arithmetic mean roughness Ra of any of the above. The arithmetic mean roughness Ra of the adhesive surface-side surfaces of both release liners may be of the same degree or may be different.

[0274] (Maximum height Rz of the adhesive side surface)

[0275] In some embodiments, the release liner (preferably a release film) has a maximum height Rz of the adhesive-side surface of 700 nm or less, which is desirable from the perspective of realizing an adhesive surface having high surface smoothness. In some embodiments, the maximum height Rz of the adhesive-side surface of the release liner is preferably about 600 nm or less, may be about 500 nm or less, may be about 400 nm or less, or may be about 300 nm or less. In addition, in some embodiments, the maximum height Rz may be, for example, about 50 nm or more, about 80 nm or more, about 100 nm or more, about 150 nm or more, or about 200 nm or more. In an adhesive sheet having a release liner configured such that a release liner is disposed on each of a first adhesive surface and a second adhesive surface, it is preferable that the adhesive surface-side surfaces of both release liners satisfy the maximum height Rz of any of the above. The maximum height Rz of the adhesive surface-side surfaces of both release liners may be approximately the same or different.

[0276] (Surface characteristics of the back side)

[0277] The arithmetic mean roughness Ra or maximum height Rz of the back surface (opposite side to the adhesive layer) of the release liner (preferably the release film) is not particularly limited. The arithmetic mean roughness Ra of the back surface of the release liner may be, for example, greater than 30 nm (e.g., greater than 35 nm, and furthermore, approximately 50 nm or more) from the perspective of productivity, etc. The maximum height Rz of the back surface of the release liner may be, for example, greater than 400 nm (e.g., approximately 500 nm or more) or greater than 800 nm (e.g., 1000 nm or more) from the perspective of productivity, etc.

[0278] The arithmetic mean roughness Ra and maximum height Rz of the release film surface can be controlled by the selection of film material, molding method, surface treatment such as release treatment, etc. For example, control of the smoothness of the layer constituting the releaseable surface (anti-blocking layer, hard coat layer, oligomer prevention layer, etc.), reduction or non-use (particle-free) of filler particles in said surface layer or release film substrate, and other adjustments to stretching conditions may be used.

[0279] The arithmetic mean roughness Ra and maximum height Rz of the surface of a release liner (preferably a release film) are measured using a non-contact surface roughness measuring device. As a non-contact surface roughness measuring device, an optical interference type surface roughness measuring device is used, and for example, a 3D optical profiler (product name "NewView 7300", manufactured by ZYGO) or an equivalent product may be used. For example, a glass plate (soda-lime glass plate manufactured by MATSUNAMI, thickness 1.3 mm) is bonded and fixed with an adhesive to the surface opposite to the measurement surface of the release liner, and the surface shape can be measured using a 3D optical profiler (product name "NewView 7300", manufactured by ZYGO) under an environment of 23°C and 50%RH.

[0280] <Uses>

[0281] The adhesive sheet disclosed herein can be used by bonding it to various substrates. The constituent material of the above-mentioned adherent (adherent material) is not particularly limited, but may include, for example, metal materials such as copper, silver, gold, iron, tin, palladium, aluminum, nickel, titanium, chromium, indium, zinc, etc., or alloys containing two or more of these; or various resin materials (typically plastic materials) such as polyimide resin, acrylic resin, polyethernitrile resin, polyethersulfone resin, polyester resin (PET resin, polyethylene naphthalate resin, etc.), polyvinyl chloride resin, polyphenylene sulfide resin, polyetheretherketone resin, polyamide resin (so-called aramid resin, etc.), polyarylate resin, fluorine resin, polycarbonate resin, cellulose-based polymer such as diacetylcellulose or triacetylcellulose, vinyl butyral polymer, liquid crystal polymer, carbon materials such as graphene, alumina, zirconia, titania, SiO2, Examples include metal oxides such as ITO (indium tin oxide) and ATO (antimony-doped tin oxide) and mixtures thereof, nitrides such as aluminum nitride, silicon nitride, titanium nitride, gallium nitride, and indium nitride and composites thereof, and inorganic materials such as alkali glass, alkali-free glass, quartz glass, borosilicate glass, and sapphire glass. The adhesive sheet disclosed herein can be attached to a member (e.g., an optical member) on which at least the surface is composed of the above materials.

[0282] The adhesive sheet disclosed herein can be used in an attachment mode that does not require a heating treatment to a temperature higher than room temperature (e.g., 20°C to 35°C) after being bonded to a substrate. Additionally, if permitted by the constituent material of the adhesive sheet (e.g., the material of the substrate) or the type of substrate, a heat treatment may be performed at least at any of the following timings: after bonding to the substrate, at the time of bonding, and before bonding. The heat treatment may be performed for purposes such as improving the adhesion of the adhesive to the substrate or promoting bonding. The heat treatment temperature may be appropriately set to obtain the desired effect within a range permitted by the constituent material of the adhesive sheet or the type of substrate, taking into account the surface condition of the substrate, etc., and may be, for example, about 100°C or lower, 80°C or lower, 60°C or lower, or 50°C or lower.

[0283] The member or material to which the adhesive sheet is attached (in the case of a double-sided adhesive sheet, at least one substrate) may have light transmittance. With such a substrate, it is easy to obtain the advantage of increasing the refractive index while suppressing the degradation of optical properties (such as transparency) by applying the technology disclosed herein. The total light transmittance of the substrate may, for example, be greater than 50% or 70% or more. In several preferred embodiments, the total light transmittance of the substrate is 80% or more, more preferably 90% or more, and even more preferably 95% or more (e.g., 95 to 100%). The adhesive sheet disclosed herein may preferably be used in an embodiment in which it is attached to a substrate (e.g., an optical member) having a total light transmittance of at least a predetermined value. The total light transmittance is measured using a commercially available transmittance meter in accordance with JIS K 7136:2000. As a transmittance meter, the product name "HAZEMETER HM-150" manufactured by Murakami Shikisai Gijutsu Genkyujo or an equivalent product is used.

[0284] The refractive index of the adhesive layer and the refractive index of the substrate may be of the same degree or different. For example, by making the refractive index of the adhesive layer relatively higher than that of the substrate, light incident from the substrate side onto the adhesive layer at an angle less than or equal to the critical angle can be refracted toward the front side, thereby increasing the front brightness. In this case, the refractive index of the substrate may be, for example, 1.55 or less, 1.50 or less, 1.48 or less, 1.45 or less, or less than 1.45, and may also be, for example, 1.10 or more, 1.20 or more, 1.30 or more, or 1.35 or more. Furthermore, according to the substrate having a relatively high refractive index compared to the adhesive layer, light incident from the adhesive layer side onto the substrate can be refracted toward the front side, thereby increasing the front brightness. In this case, the refractive index of the adherend may be, for example, 1.60 or higher, 1.65 or higher, or 1.70 or higher, and may also be, for example, 3.00 or lower, 2.50 or lower, or 2.00 or lower. Meanwhile, light reflection at the interface can be suppressed by reducing the difference in refractive index between the adhesive layer and the adherend. In this case, the refractive index of the adherend may be approximately 1.55 to 1.80, approximately 1.55 to 1.75, or approximately 1.60 to 1.70. The refractive index of the adherend can be measured in the same way as the refractive index of the adhesive.

[0285] In some preferred embodiments, the substrate may have the refractive index of any of the above-described and also the total light transmittance of any of the above-described. In an embodiment of attachment to such a substrate, the effect of the technique disclosed herein is particularly preferably exhibited.

[0286] As an example of a preferred application, optical applications may be cited. More specifically, the adhesive sheet disclosed herein may be preferably used as an optical adhesive sheet used, for example, for bonding optical members (for bonding optical members) or for manufacturing products in which said optical members are used (optical products).

[0287] The above optical member refers to a member having optical properties (e.g., polarization, photorefractive properties, photoscattering properties, photorefractive properties, phototransmittance, photoabsorption, photodiffraction, photorotation, visibility, etc.). The above optical member is not particularly limited as long as it is a member having optical properties, but examples include a member constituting a device (optical device) such as a display device (image display device) or an input device, or a member used in such devices. Examples include a polarizer, a wave plate, a phase difference plate, an optical compensation film, a brightness enhancement film, a light guide plate, a reflective film, an anti-reflective film, a hard coat (HC) film, a shock-absorbing film, an anti-fouling film, a photochromic film, a light-dampening film, a transparent conductive film (ITO film), a design film, a decorative film, a surface protection plate, a prism, a lens, a color filter, a transparent substrate, or furthermore, a member in which these are laminated (these are collectively referred to as "functional films"). In addition, the above "plate" and "film" each include a plate-like, film-like, sheet-like form, etc. For example, the "polarizing film" includes a "polarizing plate" or a "polarizing sheet," etc., and the "light guide plate" includes a "light guide film" or a "light guide sheet," etc. In addition, the above "polarizing plate" includes a circular polarizing plate.

[0288] Examples of the above display devices include liquid crystal displays, organic EL (electroluminescence) displays, micro LEDs (μLEDs), mini LEDs (miniLEDs), plasma display panels (PDPs), electronic paper, etc. Additionally, examples of the above input devices include touch panels, etc.

[0289] The above optical member is not particularly limited, but may include, for example, a member made of glass, acrylic resin, polycarbonate, polyethylene terephthalate, a metal thin film, etc. (e.g., a sheet-like, film-like, or plate-like member). Furthermore, the term "optical member" in this specification includes a member that performs a role of decoration or protection while maintaining the visibility of a display device or input device (e.g., a decorative film, a decorative film, or a surface protection film).

[0290] The technology disclosed herein may preferably be used to bond an optical film, such as a fluorescent film or a film having one or more functions including light transmission, reflection, diffusion, waveguide, light concentration, and diffraction, to another optical member (which may be another optical film). Among these, in the bonding of an optical film having at least one function among light waveguide, light concentration, and diffraction, it is preferable that the entire bulk of the bonding layer has a high refractive index, and this may be a preferred application of the technology disclosed herein.

[0291] The adhesive disclosed herein can be preferably used for bonding optical films, such as light guide films, diffusion films, fluorescent films, color-changing films, prism sheets, lenticular films, and microlens array films. In these applications, thinning and improved light extraction efficiency are required in light of the trend toward miniaturization and high performance of optical components. The adhesive disclosed herein can be preferably used as an adhesive capable of meeting these requirements. More specifically, for example, in the bonding of light guide films or diffusion films, thinning can be achieved by adjusting the refractive index of the adhesive layer as a bonding layer (e.g., making it high-refractive index). In the bonding of fluorescent films, light extraction efficiency (which can also be understood as luminous efficiency) can be improved by appropriately adjusting the difference in refractive index between the fluorescent emitter and the adhesive. In the bonding of color-changing films, scattering components can be reduced by appropriately adjusting the refractive index of the adhesive so that the difference in refractive index with the color-changing pigment becomes small, thereby contributing to improved light transmittance. In bonding prism sheets, lenticular films, microlens array films, etc., light diffraction can be controlled by appropriately adjusting the refractive index of the adhesive, thereby contributing to an improvement in brightness and / or viewing angle.

[0292] The adhesive sheet disclosed herein is preferably used in a manner in which it is attached to a substrate with a high refractive index (which may be a layer or member of the same, etc.), thereby suppressing interfacial reflection with said substrate. An adhesive sheet used in such a manner is preferably one that has a small difference in refractive index with the substrate as described above, and also has high adhesion at the interface with said substrate. Furthermore, from the perspective of increasing the homogeneity of the appearance, it is desirable that the uniformity of the thickness of the adhesive layer is high, and for example, that the surface smoothness of the adhesive surface is high. When the thickness of the substrate with a high refractive index is relatively small (for example, 5 μm or less, 4 μm or less, or 2 μm or less), suppressing reflection at the interface is particularly meaningful from the perspective of suppressing discoloration or color non-uniformity caused by interference of reflected light. As an example of such a mode of use, there is a polarizing plate having a phase difference layer comprising a polarizer, a first phase difference layer, and a second phase difference layer in that order, wherein the polarizer and the first phase difference layer are joined and / or the first phase difference layer and the second phase difference layer are joined.

[0293] In addition, the adhesive sheet disclosed herein can preferably be used in a manner attached to a light-emitting layer (e.g., a high-refractive-index light-emitting layer composed mainly of inorganic materials) such as an optical semiconductor, in that it is suitable for achieving a high refractive index. By reducing the difference in refractive index between the light-emitting layer and the adhesive layer, reflection at their interface can be suppressed, thereby improving light extraction efficiency. An adhesive sheet used in this manner preferably has an adhesive layer with a high refractive index. Furthermore, from the perspective of preventing the degradation of the self-luminous device due to moisture, it is desirable for the absorption rate of the adhesive layer to be low. From the perspective of improving brightness, it is desirable for the adhesive sheet to be low-color. This can also be advantageous from the perspective of suppressing unintentional coloration caused by the adhesive sheet.

[0294] The adhesive disclosed herein may preferably be used as a coating layer covering a lens surface, a bonding layer with a member facing the lens surface (e.g., a member having a surface shape corresponding to the lens surface), or a filling layer filled between the lens surface and the member, in a microlens or other lens member used as a component of a camera or light-emitting device (e.g., a lens member such as a microlens constituting a microlens array film or a microlens for a camera). Since the adhesive disclosed herein is suitable for achieving a high refractive index, it can reduce the difference in refractive index with a high-refractive-index lens (e.g., a lens composed of a high-refractive-index resin or a lens having a surface layer made of a high-refractive-index resin). This is advantageous from the perspective of thinning the lens and the product equipped with the lens, and can also contribute to suppressing aberrations and improving the Abbe number. The adhesive disclosed herein may also be used as a lens resin itself, for example, in a form filled in a recess or void of a suitable transparent member.

[0295] The mode of bonding optical members using the adhesive sheet disclosed herein is not particularly limited, but may include, for example, (1) a mode of bonding optical members together through the adhesive sheet disclosed herein, (2) a mode of bonding an optical member to a member other than an optical member through the adhesive sheet disclosed herein, and (3) a mode in which the adhesive sheet disclosed herein is in a form including an optical member and the adhesive sheet is bonded to an optical member or a member other than an optical member. Furthermore, in the mode of (3), the adhesive sheet in a form including an optical member may be, for example, an adhesive sheet in which the support is an optical member (e.g., an optical film). An adhesive sheet in such a form including an optical member as a support may also be understood as an adhesive optical member (e.g., an adhesive optical film). In addition, if the adhesive sheet disclosed herein is a type of adhesive sheet having a support, and the functional film is used as the support, the adhesive sheet disclosed herein may also be understood as an "adhesive type functional film" having an adhesive layer disclosed herein on at least one side of the functional film.

[0296] From the above, according to the technology disclosed herein, a laminate is provided comprising an adhesive sheet disclosed herein and a member to which the adhesive sheet is attached. The member to which the adhesive sheet is attached may have the refractive index of the adherend material described above. In addition, the difference between the refractive index of the adhesive sheet and the refractive index of the member (refractive index difference) may be the difference in refractive index between the adherend and the adhesive sheet described above. As for the member constituting the laminate, since it is as described above as the member, material, and adherend, a redundant description is not repeated.

[0297] As can be understood from the above description and the following examples, the matters disclosed by this specification include the following.

[0298] [1] An adhesive sheet comprising an adhesive layer,

[0299] having an adhesive surface formed by the above adhesive layer,

[0300] The adhesive layer is an adhesive sheet having a refractive index greater than 1.570, a total light transmittance of 86% or more, and a haze value of 3.0% or less.

[0301] [2] The adhesive layer described above is an adhesive sheet described in [1] having a thickness of 5 μm or more.

[0302] [3] An adhesive sheet described in [1] and [2] above, having a peel strength (adhesion) of 3 N / 25 mm or more against a glass plate.

[0303] [4] The adhesive surface is an adhesive sheet described in any one of [1] to [3], having an arithmetic mean roughness Ra of 100 nm or less.

[0304] [5] The adhesive layer is an adhesive sheet described in any one of [1] to [4], having an absorption rate of 1.0% or less.

[0305] [6] An adhesive sheet described in any one of [1] to [5], comprising a laminate including the adhesive layer and a light-transmitting substrate.

[0306] [7] The above light-transmitting substrate is a resin film, and is an adhesive sheet described in [6].

[0307] [8] An adhesive sheet described in any one of [1] to [5], which is a double-sided adhesive sheet formed by the adhesive layer above.

[0308] [9] An adhesive sheet described in any one of [1] to [8] above, and

[0309] A release liner disposed on the adhesive surface of the above adhesive sheet

[0310] An adhesive sheet having a release liner comprising

[0311]

[10] An adhesive composition used to form an adhesive layer of an adhesive sheet described in any one of [1] to [8] above.

[0312]

[11] An acrylic polymer (A) containing an aromatic ring-containing monomer (m1) as a monomer unit, and

[0313] An additive (H) which is an organic material with a higher refractive index than the above acrylic polymer (A) RO )

[0314] An adhesive composition comprising

[0315]

[12] The above additive (H RO An adhesive composition described in

[11] above, wherein the refractive index of ) is 1.60 or higher.

[0316]

[13] The additive (H) per 100 parts by weight of the acrylic polymer (A) RO The adhesive composition described in

[11] or

[12] , wherein the content of ) is greater than 0 parts by weight and less than or equal to 60 parts by weight.

[0317]

[14] The above additive (H RO The adhesive composition described in any one of

[11] to

[13] comprises at least one compound selected from the group consisting of aromatic ring-containing compounds and heterocyclic ring-containing compounds.

[0318]

[15] The above additive (H RO ) is an adhesive composition described in any one of

[11] to

[14] , comprising a compound having two or more aromatic rings within one molecule.

[0319]

[16] The above additive (H RO ) is a compound having two or more aromatic rings within the above-mentioned molecule,

[0320] (i) comprising a structure in which two non-condensing aromatic rings are directly chemically bonded, and

[0321] (ii) A structure comprising two condensed aromatic rings

[0322] An adhesive composition described in

[15] comprising a compound satisfying at least one of the following.

[0323]

[17] An adhesive composition described in any one of

[11] to

[16] , wherein the content of the aromatic ring-containing monomer (m1) in the monomer component constituting the acrylic polymer (A) is 50% by weight or more.

[0324]

[18] In the monomer component constituting the acrylic polymer (A), the content of the aromatic ring-containing monomer (m1) is greater than 70% by weight and less than 100% by weight,

[0325] An adhesive composition described in any one of

[11] to

[17] , wherein 50% or more of the above aromatic ring-containing monomer (m1) is a monomer having a glass transition temperature of 10°C or lower.

[0326]

[19] A pressure-sensitive adhesive composition described in any one of

[11] to

[18] , wherein the monomer component constituting the acrylic polymer (A) further contains a monomer (m2) having at least one of a hydroxyl group and a carboxyl group.

[0327]

[20] An adhesive composition described in any one of

[11] to

[18] used to form an adhesive layer of an adhesive sheet described in any one of [1] to [8].

[0328]

[21] An adhesive formed from an adhesive composition described in any one of

[11] to

[20] above, and having a refractive index higher than 1.570.

[0329]

[22] An adhesive sheet comprising an adhesive layer formed by an adhesive formed from any one of

[11] to

[20] .

[0330]

[23] An adhesive sheet described in

[22] , wherein the haze value of the adhesive layer is 1.0% or less.

[0331]

[24] An interlayer sheet used for optical applications, placed between layers of a laminate, and

[0332] It comprises a viscoelastic layer V1 having a refractive index n1 of 1.570 or higher, and also

[0333] One with a total light transmittance of 86% or higher;

[0334] A haze value of 1.0% or less; and,

[0335] A storage modulus G' at 25℃ of 30 kPa to 700 kPa;

[0336] Interlayer sheet satisfying

[0337]

[25] An interlayer sheet described in

[24] having a thickness of 5㎛ or more.

[0338]

[26] The above viscoelastic layer V1 comprises a main polymer and a plasticizing material having a molecular weight lower than that of the main polymer, an interlayer sheet as described in

[24] or

[25] .

[0339]

[27] An interlayer sheet described in

[26] , wherein the weight average molecular weight of the plasticizing material is 30,000 or less.

[0340]

[28] Further comprising a viscoelastic layer V2 laminated on the above viscoelastic layer V1, and

[0341] Storage modulus G' of the above viscoelastic layer V2 at 25°C V2 is the storage modulus G' of the above viscoelastic layer V1 at 25°C V1 A lower interlayer sheet as described in any of

[24] to

[27] above.

[0342]

[29] An interlayer sheet described in

[28] , wherein the refractive index n2 of the viscoelastic layer V2 is lower than the refractive index n1 of the viscoelastic layer V1.

[0343]

[30] The above viscoelastic layer V1 is an interlayer sheet described in any one of

[24] to

[29] , which is a layer formed from an adhesive composition described in any one of

[11] to

[18] .

[0344]

[31] The above viscoelastic layer V1 is an interlayer sheet described in any one of

[24] to

[29] , which is an adhesive layer in an adhesive sheet described in any one of [1] to [5].

[0345]

[32] An interlayer sheet described in any one of

[24] to

[31] above, and

[0346] Resin film laminated on the above interlayer sheet

[0347] An optical laminate comprising

[0348]

[33] An interlayer sheet described in any one of

[24] to

[31] above, and

[0349] A release liner covering at least one surface of the above-mentioned interlayer sheet

[0350] An interlayer sheet having a release liner comprising

[0351] Examples

[0352] Several embodiments relating to the present invention are described below, but the present invention is not intended to be limited to those described in these embodiments. Furthermore, in the following description, "parts" and "%" indicating usage or content are based on weight unless otherwise specified.

[0353] <Example 1>

[0354] (Preparation of acrylic polymer solution)

[0355] In a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a cooler, 99 parts of m-phenoxybenzyl acrylate (manufactured by Kyoesha Chemical Co., Ltd., trade name "Light Acrylate POB-A", refractive index: 1.566, Tg of homopolymer: -35°C; hereinafter abbreviated as "POB-A") and 1 part of 4-hydroxybutyl acrylate (4HBA) were added as monomer components, 0.2 parts of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator, and 100 parts of toluene as a polymerization solvent were added, nitrogen gas was introduced while stirring gently, and the liquid temperature inside the flask was maintained at around 60°C for 6 hours to carry out a polymerization reaction to prepare a solution (50%) of acrylic polymer A1. The above acrylic polymer A1 is based on the composition of the monomer component, with a Tg (i.e., Tg T ) is -35℃, and Tg based on the composition of the aromatic ring-containing monomer (i.e., Tg m1 ) is -35℃.

[0356] (Preparation of adhesive composition)

[0357] A solution (50%) of the above acrylic polymer A1 was diluted to 30% with ethyl acetate, and to 334 parts (100 parts of non-volatile matter) of this solution, 10 parts (0.1 parts of non-volatile matter) of a 1% ethyl acetate solution of an isocyanurate of hexamethylene diisocyanate (manufactured by Dosoh Co., Ltd., trade name "Coronate HX", trifunctional isocyanate compound) was added as a crosslinking agent, 2 parts of acetylacetone as a crosslinking retardant, and 1 part (0.01 parts of non-volatile matter) of a 1% ethyl acetate solution of ferric nasem as a crosslinking catalyst were added and stirred to prepare an acrylic adhesive composition C1.

[0358] (Production of adhesive sheets)

[0359] The acrylic adhesive composition C1 prepared above was applied to the silicone-treated surface of a polyethylene terephthalate (PET) film R1 (thickness 50 μm, arithmetic mean roughness of the silicone-treated surface Ra 21 nm, maximum height Rz 233 nm) on which silicone treatment was performed on one side, and heated at 130°C for 2 minutes to form an adhesive layer with a thickness of 20 μm. Next, the silicone-treated surface of a PET film R2 (thickness 25 μm, arithmetic mean roughness of the silicone-treated surface Ra 15 nm, maximum height Rz 180 nm) on which silicone treatment was performed on one side was bonded to the surface of the adhesive layer (first adhesive surface). In this way, a substrate-free double-sided adhesive sheet S1 consisting of the adhesive layer was obtained. Both sides of the adhesive sheet S1 are protected by PET films (release liners) R1 and R2. The release liner R2 bonded to the first adhesive surface is relatively light compared to the release liner R1 (the release liner to which the adhesive composition is applied) that protects the second adhesive surface.

[0360] <Examples 2 to 3, 7 to 8, 10 to 14>

[0361] Solutions of acrylic polymers A2 to 3, 7 to 8, and 10 to 14 for each example were prepared in the same manner as the acrylic polymer solution in Example 1, except that the composition of the monomer components was changed as shown in Table 1.

[0362] Acrylic adhesive compositions C2 to 3, 7 to 8, and 10 to 14 for each example were prepared in the same manner as the adhesive composition in Example 1, except that a solution of the acrylic polymer for each example was used instead of the solution of the acrylic polymer A1.

[0363] Adhesive sheets (non-substrate double-sided adhesive sheets consisting of an adhesive layer) S2 to 3, 7 to 8, and 10 to 14 for each example were produced in the same manner as the adhesive sheet in Example 1, except that the acrylic adhesive composition for each example was used instead of the acrylic adhesive composition C1, and the thickness of the adhesive layer was set as shown in Table 1.

[0364] In addition, regarding the composition of monomer components shown in Table 1, “NMT-A” represents 1-naphthylmethylacrylate (manufactured by Kyoei Chemical Co., Ltd., trade name “Light Acrylate NMT-A”, refractive index: 1.595, Tg of homopolymer: 31℃), HEA represents 2-hydroxyethylacrylate, BA represents n-butylacrylate, and 2EHA represents 2-ethylhexylacrylate.

[0365] <Example 4>

[0366] A solution (50%) of the acrylic polymer A3 prepared in Example 3 is diluted with 30% ethyl acetate, and to 334 parts (100 parts of non-volatile matter) of this solution, an additive (H RO As a crosslinking agent, 5 parts of 6-acryloyloxymethyldinaphthothiophene (dinaphthothiophene-6-methylacrylate, manufactured by Sugai Kagaku Kogyo Co., Ltd., trade name "6MDNTA", refractive index 1.75), 10 parts of a 1% ethyl acetate solution of an isocyanurate of hexamethylene diisocyanate (manufactured by Dosoh Co., Ltd., trade name "Coronate HX", trifunctional isocyanate compound) as a crosslinking agent (non-volatile content 0.1 parts), 2 parts of acetylacetone as a crosslinking retardant, and 1 part of a 1% ethyl acetate solution of ferric nasem as a crosslinking catalyst (non-volatile content 0.01 parts) were added and stirred to prepare an acrylic adhesive composition C4.

[0367] Except for using acrylic adhesive composition C4 instead of acrylic adhesive composition C1 and making the thickness of the adhesive layer 25 μm, an adhesive sheet (a double-sided adhesive sheet without a substrate consisting of an adhesive layer) S4 according to the present example was produced in the same manner as the adhesive sheet in Example 1.

[0368] <Examples 5 to 6>

[0369] Additive (H RO Acrylic adhesive compositions C5 and C6 for Examples 5 and 6 were prepared in the same manner as the acrylic adhesive composition C4 in Example 4, except that the type of ) and the amount used per 100 parts of acrylic polymer (phr; per hundred resin) were changed as shown in Table 1. Here, “BPFL” in Table 1 represents 9,9-bis(4-hydroxyphenyl)fluorene (manufactured by Osaka Gas Chemical Co., Ltd., refractive index 1.68), and “BAFL” represents 9,9-bis(4-aminophenyl)fluorene (manufactured by Osaka Gas Chemical Co., Ltd., refractive index 1.73).

[0370] Adhesive sheets (substrate-free double-sided adhesive sheets consisting of an adhesive layer) according to Examples 5 and 6 were produced in the same manner as the adhesive sheet in Example 4, except that acrylic adhesive compositions C5 and C6 were used instead of acrylic adhesive composition C4, respectively.

[0371] <Example 9>

[0372] A solution (50%) of the acrylic polymer A8 prepared in Example 8 was diluted with 30% ethyl acetate, and to 334 parts (100 parts of non-volatile matter) of this solution, an additive (H ROAn acrylic adhesive composition C9 was prepared by adding 10 parts of BPFL as a crosslinking agent, 10 parts of a 1% ethyl acetate solution of an isocyanurate of hexamethylene diisocyanate (manufactured by Dososa, trade name "Coronate HX", trifunctional isocyanate compound) as a crosslinking agent (non-volatile content 0.1 parts), 2 parts of acetylacetone as a crosslinking retardant, and 1 part of a 1% ethyl acetate solution of ferric nasem as a crosslinking catalyst (non-volatile content 0.01 parts) and stirring and mixing.

[0373] Except for using acrylic adhesive composition C9 instead of acrylic adhesive composition C8, an adhesive sheet (a double-sided adhesive sheet without a substrate consisting of an adhesive layer) S9 according to the present example was produced in the same manner as the adhesive sheet in Example 8.

[0374] <Example 15>

[0375] A solution (40%) of acrylic polymer A14 was prepared in the same manner as the acrylic polymer solution in Example 1, except that the composition of the monomer components was changed to 90 parts of 2-ethylhexyl acrylate (2EHA) and 10 parts of 4HBA.

[0376] A solution (40%) of the above acrylic polymer A14 was diluted with 20% ethyl acetate, and to 500 parts (100 parts of non-volatile content) of this solution, 10 parts based on solid content of a zirconia particle dispersion, 10 parts (0.1 parts of non-volatile content) of a 1% ethyl acetate solution of an isocyanurate of hexamethylene diisocyanate (manufactured by Dosoh Co., Ltd., trade name "Coronate HX", trifunctional isocyanate compound) as a crosslinking agent, 2 parts of acetylacetone as a crosslinking retardant, and 1 part (0.01 parts of non-volatile content) of a 1% ethyl acetate solution of ferric nasem as a crosslinking catalyst were added and stirred to prepare an acrylic adhesive composition C15. As the above zirconia particle dispersion, a surface-treated zirconia particle dispersion was used in which surface-treated zirconia particles (average particle size 20 nm, solid content refractive index: 1.64, surface treatment: carboxylic acid-based / phosphate-based hydrophobization treatment, manufactured by Kyoesha Chemical Co., Ltd.) were dispersed in propylene glycol monomethyl ether (PGME).

[0377] Except for using acrylic adhesive composition C15 instead of acrylic adhesive composition C14, an adhesive sheet (a double-sided adhesive sheet without a substrate consisting of an adhesive layer) S15 according to Example 15 was produced in the same manner as the adhesive sheet in Example 14.

[0378] The obtained adhesive sheet was used for the following measurements and evaluations after being sufficiently adapted to an environment of 23°C and 50%RH.

[0379] <Measurement and Evaluation (1)>

[0380] (Refractive index)

[0381] For each example, the refractive index of the adhesive layer (inorganic double-sided adhesive sheet) was measured using an Abbe refractive index meter (manufactured by ATAGO, model “DR-M4”) under conditions of a measurement wavelength of 589 nm and a measurement temperature of 25°C. The results are shown in Table 1.

[0382] (Total light transmittance and haze value)

[0383] For each example, a test specimen in which the adhesive layer was bonded to alkali-free glass (thickness 0.8 to 1.0 mm, total light transmittance 92%, haze 0.4%) was used, and the total light transmittance and haze of the test specimen were measured using a haze meter (manufactured by Kijutsu Genkyujo Murakami, trade name "HAZEMETER HM-150") under a measurement environment of 23°C. The value obtained by subtracting the total light transmittance and haze of the alkali-free glass from the measured value was taken as the total light transmittance and haze value of the adhesive layer. The results are shown in Table 1.

[0384] (Absorption rate)

[0385] The absorption rate of the adhesive for each example was measured by the method described above. The results are shown in Table 1. In addition, the absorption rate of Example 13 was not measured.

[0386] In addition, the storage modulus G' (25) of the adhesive layer for each example was measured using the method described above, and it was confirmed that in Examples 1 to 14, it was 350 kPa or less. On the other hand, the adhesive layer of Example 15, in which the refractive index was improved by incorporating inorganic particles of high refractive index, had a storage modulus G' (25) of 750 kPa, which was high, and lacked flexibility and adhesiveness.

[0387]

[0388] <Example 16>

[0389] Except for adjusting the amount of acrylic adhesive composition C3 applied so as to form an adhesive layer with a thickness of 5 μm, the non-material double-sided adhesive sheet S16 according to the present example was obtained in the same manner as the non-material double-sided adhesive sheet S3 according to Example 3.

[0390] <Measurement and Evaluation (2)>

[0391] For several of the adhesive sheets prepared above, the following measurements and evaluations were also performed. The results are shown in Table 2.

[0392] (Arithmetic mean roughness (Ra) and maximum height (Rz) of the adhesive surface)

[0393] A double-sided adhesive sheet without a substrate for each example was cut to a size of 150 mm in length and 50 mm in width, along with release liners R1 and R2 protecting the first and second adhesive surfaces, to produce a measurement sample. The side of the release liner R1 of the measurement sample was fixed to a test plate, and using a tensile testing machine (device name "Autograph AG-IS", manufactured by Shimadzu Seisakusho), the release liner R2 was peeled from the first adhesive surface of the measurement sample to expose the first adhesive surface under conditions of 23°C, 50%RH atmosphere, tensile speed of 300 mm / min, and peeling angle of 180°. After standing for 30 minutes, the surface shape of the first adhesive surface was measured using a 3D optical profiler (product name "NewView 7300", manufactured by ZYGO) under an environment of 23°C and 50%RH. The arithmetic surface roughness Ra was calculated from the measured data in accordance with JIS B 0601-2001.

[0394] In addition, the maximum height (Rz) was calculated as the sum of the height Rp of the highest peak above the average line of the roughness curve and the depth Rv of the deepest valley below the average line, for the data (roughness curve) obtained by the above measurement. The measurement conditions are as follows.

[0395] Measurements of Ra and Rz were performed 5 times (i.e., N=5), and the average value was adopted.

[0396] [Measurement Conditions]

[0397] Measurement area: 5.62 mm × 4.22 mm

[0398] (Objective: 2.5x, Internal lens: 0.5x)

[0399] Interpretation Mode:

[0400] Remove: Cylinder

[0401] Data Fill: ON(Max: 25)

[0402] Remove Spikes: ON(xRMS: 1)

[0403] Filter: OFF

[0404] (Optical distortion)

[0405] A commercially available mirror (thickness 2 mm) made by silver plating on a glass plate was prepared, and the mirror was used after confirming that there was no distortion by viewing it with the naked eye and projecting a reflection onto a screen in the same manner as described below using the mirror alone. In a clean room, the surface of the mirror was wiped with a clean cloth to remove foreign matter, and then a release film R2 was peeled off from the non-material double-sided adhesive sheet for each example to expose the first adhesive surface. The mirror was then attached with appropriate tension to prevent foreign matter, bubbles, or strips of deformation from forming on the surface of the mirror, and a degassing treatment was performed using a pressurized degassing device (autoclave) to remove the influence of minute bubbles (treatment conditions: 50°C, 0.5 MPa, 30 min). After cooling at room temperature for at least 30 minutes, the release film R1 was peeled off to expose the second adhesive surface, thereby producing an optical distortion evaluation sample (a laminate consisting of an adhesive sheet and a mirror). The evaluation sample was positioned so that its adhesive sheet side faced the point light source, and the angle with respect to the light ray from the point light source was approximately 45 degrees. A white screen was installed at the end of the light ray to project the reflected image. As the point light source, the product name "Xenon Lamp C2577" or an equivalent product manufactured by Hamamatsu Photonics Co., Ltd. could be used, and the product name "Xenon Lamp C2577" was used in this experiment. The point light source, evaluation sample, and screen were positioned so that the distance between the evaluation sample and the point light source, and the distance between the evaluation sample and the screen, were each approximately 50 cm.

[0406] The above point light source was turned on, and the image reflected from the sample and projected onto the screen was observed with the naked eye, thereby evaluating the presence and degree of optical distortion at the following three levels.

[0407] E: No optical distortion visible.

[0408] A: Slight optical distortion is visible, but it is within a practically acceptable range.

[0409] P: Clear optical distortion is visible.

[0410] (Peel strength against glass plate)

[0411] Under a measurement environment of 23℃ and 50%RH, a release liner was peeled off from one side of the adhesive sheet, and a PET film with a thickness of 50㎛ was bonded and laminated, and then cut to a size of 25mm in width and 100mm in length to be used as a test specimen. The release liner on the other side of the test specimen was peeled off, and a 2kg roller was pressed once back and forth against the surface of an alkali glass plate (manufactured by Matsunami Glass Kogyo Co., Ltd., thickness 1.35mm, polished blue plate) as a substrate. This was left for 30 minutes under the same conditions, then placed in a pressurized degassing device (autoclave) and subjected to autoclave treatment for 30 minutes under conditions of a temperature of 50°C and a pressure of 0.5 MPa, and then left for 24 hours under an atmosphere of 23°C and 50%RH. Afterward, the peel strength (adhesion) [N / 25 mm] was measured using a universal tensile compression tester in accordance with JIS Z 0237:2000 under conditions of a tensile speed of 300 mm / min and a peel angle of 180 degrees. As the universal tensile compression tester, the "Tensile Compression Tester, TG-1kN" manufactured by Minebea was used.

[0412]

[0413] The adhesive sheets of Examples 1 to 13 shown in Table 1 exhibited a high refractive index exceeding 1.570 and also exhibited high transparency. Furthermore, as shown in Table 2, they exhibited practical peel strength as adhesives and had excellent surface smoothness. In comparison between Example 3 and Example 16, which used the same adhesive composition, Example 16 yielded better results in the evaluation of optical distortion. Additionally, although not shown in Table 2, the absorption rate of Example 16 was 0.2%.

[0414] Meanwhile, Example 15, in which the refractive index was improved by incorporating inorganic particles of high refractive index, had significantly lower transparency compared to Examples 1 to 13 (in particular, the haze was significantly higher), and as shown in Table 2, had low surface smoothness and showed clear optical distortion, and also did not exhibit adhesive performance (peeling strength) suitable for practical use as an adhesive.

[0415] <Examples 17, 18, 23>

[0416] Acrylic adhesive compositions were prepared by preparing solutions of acrylic polymers for each of Examples 17, 18, and 23 in the same manner as Example 1, except that the composition of the monomer components was as shown in Table 3. Acrylic adhesive compositions for each example were prepared by using the acrylic adhesive composition for each example instead of acrylic adhesive composition C1, and by making the thickness of the adhesive layer 25 μm, in the same manner as the adhesive sheet prepared in Example 1.

[0417] In addition, regarding the composition of monomer components shown in Table 3, "BZA" represents benzyl acrylate (manufactured by Osaka Yuki Kagaku Kogyo Co., Ltd., trade name "Viscot #160", refractive index (nD20): 1.519, homopolymer Tg: 6°C), "PEA" represents phenoxyethyl acrylate (manufactured by Osaka Yuki Kagaku Kogyo Co., Ltd., trade name "Viscot #192", refractive index (nD20): 1.517, homopolymer Tg: 2°C), "P2H-A" represents phenoxydiethylene glycol acrylate (manufactured by Kyoei Kagaku Kogyo Co., Ltd., trade name "Light Acrylate P2H-A", refractive index: 1.510, homopolymer Tg: -35°C), and HEMA represents 2-hydroxyethyl methacrylate, CBA represents ethyl carbitol acrylate.

[0418] <Example 19>

[0419] A solution of acrylic polymer A19 according to the present example was prepared in the same manner as in Example 1, except that the composition of the monomer components was as shown in Table 3. A solution of acrylic polymer A19 was used instead of a solution of acrylic polymer A3, and an additive (H RO An acrylic adhesive composition according to the present example was prepared and an adhesive sheet was produced by using 10 phr of 2,12-diallyloxydinaphthiophen (manufactured by Sugai Kagaku Kogyo Co., Ltd., abbreviation: 2,12-DAODNT, refractive index: 1.729) as the adhesive, in the same manner as in Example 4.

[0420] <Examples 20 to 22>

[0421] Solutions of acrylic polymers for each of Examples 20 to 22 were prepared in the same manner as in Example 1, except that the composition of the monomer components was as shown in Table 3. Solutions of acrylic polymers for each example were used instead of the solution of acrylic polymer A3, and additives (H ROAcrylic adhesive compositions for each example were prepared and adhesive sheets were produced in the same manner as in Example 4, except that 20 phr of 6-ethyl acrylate-dinaphtho[2,1-b:1',2'-d]thiophene (6-acryloyloxyethyldinaphthothiophene manufactured by Sugai Kagaku Kogyo Co., Ltd., abbreviation: 6EDNTA, refractive index: 1.722) was used.

[0422] After sufficiently exposing the adhesive sheets obtained by Examples 17 to 23 to an environment of 23°C and 50%RH, measurements and evaluations of each item were performed in the same manner as described in “Measurement and Evaluation (1)” above. The results are shown in Table 3.

[0423]

[0424] The adhesive sheets of Examples 17 to 23 shown in Table 3 all exhibited a high refractive index exceeding 1.570 and also exhibited high transparency. Among these, the adhesive sheet of Example 23 had a harder texture and a higher absorption rate compared to the adhesive sheets of Examples 17 to 22.

[0425] From the above, the adhesive sheets of Examples 1 to 13, Examples 16, and Examples 17 to 23 (substrate-free double-sided adhesive sheets made of an adhesive layer) are suitable for applications such as bonding optical members (e.g., optical films having at least one function among light guidance, light collection, and diffraction) in that they have a high refractive index while suppressing the degradation of optical properties.

[0426] Although specific embodiments of the present invention have been described in detail above, they are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and alterations of the specific embodiments exemplified above. Explanation of the symbols

[0427] 1, 2: Adhesive sheet 10: Adhesive layer 10A: First surface (adhesive surface) 10B: Second surface 20: Support material 20A: 1st side 20B: Second side (back) 30, 31, 32: Release liner 50: Adhesive sheet having a release liner 70: Optical component 100: A member having an adhesive sheet

Claims

Claim 1 An adhesive sheet comprising an adhesive layer, and having an adhesive surface formed by the adhesive layer, wherein the adhesive layer has a refractive index greater than 1.570, a total light transmittance of 86% or more, and a haze value of 3.0% or less, wherein the adhesive layer comprises an acrylic polymer as a base polymer, and the monomer component constituting the acrylic polymer comprises 50% by weight or more of an aromatic ring-containing monomer, and additionally comprises a hydroxyl group-containing monomer, wherein the monomer component satisfies at least one of the following conditions: (A) more than 50% by weight of the hydroxyl group-containing monomer is hydroxyalkyl acrylate, and the aromatic ring-containing monomer content having a Tg of 0°C or less in the monomer component is 3% by weight or more; and (B) the hydroxyl group-containing monomer comprises 4-hydroxybutyl acrylate. Claim 2 In claim 1, the adhesive layer is an adhesive sheet having a thickness of 5 μm or more. Claim 3 An adhesive sheet according to claim 1 or 2, having a peel strength of 3N / 25mm or more against a glass plate. Claim 4 In claim 1 or 2, the adhesive surface is an adhesive sheet having an arithmetic mean roughness Ra of 100 nm or less. Claim 5 In claim 1 or 2, the adhesive layer is an adhesive sheet having an absorption rate of 1.0% or less. Claim 6 An adhesive sheet according to claim 1 or 2, comprising a laminate including an adhesive layer and a light-transmitting substrate. Claim 7 In claim 6, the light-transmitting substrate is an adhesive sheet that is a resin film. Claim 8 An adhesive sheet according to claim 1 or 2, which is a double-sided adhesive sheet formed of the adhesive layer. Claim 9 An adhesive sheet having a release liner comprising an adhesive sheet described in claim 1 or 2 and a release liner disposed on the adhesive surface of the adhesive sheet.

Citation Information

Patent Citations

  • Self-adhesive sheet

    JP2011153169A

  • Optical self-adhesive composition, optical self-adhesive layer and optical self-bondable laminate

    JP2012167187A

  • Cloud point-resistant adhesives and laminates

    KR1020110068972A

  • Adhesive agent sheet having transparent adhesive agent layer

    WO2015108160A1

  • Optics adhesive composition, optics adhesive sheet and optical product

    JP2015081288A